Biodegradable resin composition and biodegradable yarn including the same

By using resin compositions of diol, aromatic dicarboxylic acid and aliphatic dicarboxylic acid, the problem of discharge of harmful substances and difficulty in rapid decomposition during incineration of polymer materials is solved, and a yarn with improved mechanical properties and biodegradability is developed. Wire and fiber aggregates, enabling rapid biodegradation and environmentally friendly material solutions.

CN119145095APending Publication Date: 2024-12-17SK LEAVEO CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202410754940.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-16
Filing Date
2024-06-12
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing polymer materials emit harmful substances during incineration, and naturally decomposition takes hundreds of years, making it difficult to decompose quickly, resulting in environmental pollution problems.

Method used

A biodegradable resin composition, including diols, aromatic dicarboxylic acids and aliphatic dicarboxylic acids, has been developed with appropriate crystallization temperatures and melt indexes for the production of yarns and fibers with improved mechanical properties. Gathering.

Benefits of technology

Rapid biodegradation of yarn and fiber aggregates is achieved, environmental pollution is reduced, and the mechanical properties and biodegradability of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119145095A_ABST
    Figure CN119145095A_ABST
Patent Text Reader

Abstract

The present invention relates to a biodegradable resin composition and a biodegradable yarn comprising the same. The present invention relates to a biodegradable yarn comprising: a first biodegradable resin composition comprising a first biodegradable resin wherein the first biodegradable resin comprises a diol, an aromatic dicarboxylic acid and an aliphatic dicarboxylic acid, and the first biodegradable resin composition has a melt index of from 6 g / 10 minutes to 15 g / 10 minutes at 190 DEG C, and a crystallization temperature of from 40 DEG C to 85 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a biodegradable resin composition, a biodegradable yarn comprising the same, and a biodegradable fiber aggregate comprising the same. Background Art

[0002] Recently, due to the increasing concern about environmental issues, there is a need to solve the disposal problem of various household products, especially disposable products. Specifically, polymer materials are inexpensive and have excellent processability and other characteristics, so they are widely used to produce various products such as films, fibers, packaging materials, bottles, containers, etc., but have the disadvantage that they emit harmful substances when incinerated at the end of the product's life, and complete natural decomposition takes hundreds of years depending on its type.

[0003] In order to overcome these limitations of polymers, people are actively studying biodegradable polymers that decompose quickly. As biodegradable polymers, polylactic acid (PLA), polybutylene adipate terephthalate (PBAT), polybutylene succinate (PBS), etc. are used.

[0004] Such a first biodegradable resin composition is disclosed in Korean Patent Application Publication No. 2012-0103158. Summary of the invention

[0005] Technical issues

[0006] Therefore, the present invention has been made in view of the above problems, and an object of the present invention is to provide a yarn having improved mechanical properties and improved biodegradability, and a biodegradable resin composition included therein.

[0007] Technical Solutions

[0008] According to one aspect of the present invention, the above and other objects can be achieved by providing: a biodegradable yarn, comprising: a first biodegradable resin composition comprising a first biodegradable resin, wherein the first biodegradable resin comprises a diol, an aromatic dicarboxylic acid and an aliphatic dicarboxylic acid, and the first biodegradable resin composition has a melt index of 6 g / 10 min to 15 g / 10 min at 190°C, and a crystallization temperature of 40°C to 85°C.

[0009] The biodegradable yarn according to the embodiment may include a filament including: a core including the second biodegradable resin composition and having an elongated shape; and a sheath including the first biodegradable resin composition and surrounding an outer peripheral surface of the core.

[0010] The biodegradable yarn according to the embodiment may further include a second biodegradable resin composition, wherein the second biodegradable resin composition includes at least one selected from the group consisting of polybutylene succinate, polylactic acid, polybutylene adipate, polybutylene succinate adipate, polybutylene succinate terephthalate, polyhydroxybutyrate-valerate, polycaprolactone and polybutylene succinate adipate terephthalate.

[0011] In the biodegradable yarn according to the embodiment, the first biodegradable resin composition may have a crystallization temperature of 45°C to 80°C.

[0012] In the biodegradable yarn according to the embodiment, the first biodegradable resin composition may have a melt index of 6 g / 10 min to 35 g / 10 min at 190° C.

[0013] In the biodegradable yarn according to the embodiment, the melt index reduction (MID) of the first biodegradable resin composition may be 0.4 g / 10 min° C. to 1.5 g / 10 min° C., as represented by the following Equation 1:

[0014] [Equation 1]

[0015] MID=(MI2-MI1) / (T2-T1)

[0016] Wherein, T1 is 190°C and T2 is 250°C,

[0017] MI1 is the melt index when the temperature of the first biodegradable resin composition is T1, and

[0018] MI2 is a melt index when the temperature of the first biodegradable resin composition is T2.

[0019] In the biodegradable yarn according to the embodiment, the tensile strength of the biodegradable yarn may be 1.5 gf / denier to 6 gf / denier, and the elongation at break may be 20% to 200%.

[0020] According to another aspect of the present invention, a biodegradable resin composition is provided, comprising: a biodegradable resin, wherein the biodegradable resin comprises a diol, an aromatic dicarboxylic acid and an aliphatic dicarboxylic acid, and the biodegradable resin composition has a melt index of 6 g / 10 min to 15 g / 10 min at 190° C., and a crystallization temperature of 40° C. to 85° C.

[0021] The biodegradable resin composition according to an embodiment may further include a crystallization temperature adjuster.

[0022] In the biodegradable resin composition according to the embodiment, the content of the terminal group in the biodegradable resin may be 20 eq / ton or more and less than 60 eq / ton.

[0023] In the biodegradable resin composition according to the embodiment, the melt index reduction (MID) of the biodegradable resin composition may be 0.4 g / 10 min.° C. to 1.5 g / 10 min.° C., as represented by the following Equation 1:

[0024] [Equation 1]

[0025] MID=(MI2-MI1) / (T2-T1)

[0026] T1 is 190°C, and T2 is 250°C,

[0027] MI1 is the melt index when the temperature of the first biodegradable resin composition is T1, and

[0028] MI2 is a melt index when the temperature of the first biodegradable resin composition is T2.

[0029] In the biodegradable resin composition according to the embodiment, the number average molecular weight of the biodegradable resin may be 20000 g / mol to 35000 g / mol.

[0030] In the biodegradable resin composition according to an embodiment, the biodegradable resin composition may have a melt index of 20 g / 10 min to 90 g / 10 min at 230° C.

[0031] In the biodegradable resin composition according to an embodiment, the biodegradable resin composition may have a melt index of 40 g / 10 min to 120 g / 10 min at 250° C.

[0032] According to yet another aspect of the present invention, a biodegradable fiber aggregate is provided, comprising a biodegradable yarn, wherein the biodegradable yarn comprises a first biodegradable resin composition comprising a first biodegradable resin, the first biodegradable resin comprising a diol, an aromatic dicarboxylic acid and an aliphatic dicarboxylic acid, and the first biodegradable resin composition has a melt index of 6 g / 10 min to 15 g / 10 min at 190°C and a crystallization temperature of 40°C to 85°C.

[0033] In the biodegradable fiber aggregate according to the embodiment, the melt index reduction (MID) of the first biodegradable resin composition may be 0.4 g / 10 min° C. to 1.5 g / 10 min° C., as represented by the following Equation 1:

[0034] [Equation 1]

[0035] MID=(MI2-MI1) / (T2-T1)

[0036] T1 is 190°C, and T2 is 250°C,

[0037] MI1 is the melt index when the temperature of the first biodegradable resin composition is T1, and

[0038] MI2 is a melt index when the temperature of the first biodegradable resin composition is T2.

[0039] In the biodegradable fiber aggregate according to the embodiment, the first biodegradable resin may have a number average molecular weight of 20000 g / mol to 35000 g / mol.

[0040] In the biodegradable fiber aggregate according to the embodiment, the first biodegradable resin composition may have a melt index of 20 to 90 g / 10 min at 230° C.

[0041] In the biodegradable fiber aggregate according to the embodiment, the first biodegradable resin composition may have a melt index of 40 to 120 g / 10 min at 250° C.

[0042] In the biodegradable fiber aggregate according to the embodiment, the content of the terminal group in the biodegradable resin may be 20 eq / ton or more and less than 60 eq / ton.

[0043] Beneficial effects

[0044] The biodegradable resin composition according to an embodiment may include a first biodegradable resin composition including a first biodegradable resin, wherein the first biodegradable resin includes a diol, an aromatic dicarboxylic acid, and an aliphatic dicarboxylic acid.

[0045] Since the first biodegradable resin composition includes the first biodegradable resin, it may have properties suitable for spinning.

[0046] In particular, the first biodegradable resin composition may have an appropriate crystallization temperature. Therefore, the first biodegradable resin composition may be easily spun to produce a biodegradable yarn.

[0047] In addition, the first biodegradable resin composition may have an appropriate melt index. Therefore, the first biodegradable resin composition may be easily spun to produce a biodegradable yarn.

[0048] In addition, the first biodegradable resin composition may have an appropriate MID. Therefore, the first biodegradable resin composition may be easily spun to produce a biodegradable yarn.

[0049] In addition, the first biodegradable resin composition may have an appropriate number of carboxyl terminal groups. Therefore, the first biodegradable resin composition may be easily spun to produce a biodegradable yarn. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 A biodegradable yarn according to an embodiment is shown.

[0051] Figure 2 A cross section of a biodegradable yarn according to an embodiment is shown.

[0052] Figure 3 A biodegradable yarn according to another embodiment is shown.

[0053] Figure 4 A schematic diagram of an apparatus for producing a first biodegradable resin composition according to an embodiment is shown.

[0054] Figure 5 An apparatus for producing a biodegradable yarn according to an embodiment is shown.

[0055] Figure 6 A cross section of a spinning block according to an embodiment is shown. DETAILED DESCRIPTION

[0056] Hereinafter, the present invention is described in detail through embodiments. These embodiments are not provided to limit the contents described below, and can be modified into various forms as long as the gist of the present invention is not changed.

[0057] In this specification, when a part "includes (comprising)" a certain component, this means that it may further include (include) other components, rather than excluding other components, unless explicitly stated to the contrary. In addition, unless otherwise specified, in all cases, the numerical ranges representing the physical property values, sizes, etc. of the components described in this specification should be understood as being modified by the term "about".

[0058] In addition, when it is said that this specification or application "includes (comprising)" a certain element, this means that other components may be further included (comprising) rather than excluding other components, unless explicitly stated to the contrary. In addition, unless otherwise specified, all numerical ranges representing the physical property values, dimensions, etc. of the components described in this specification or application should be understood to be modified by the term "about" in all cases. In addition, "ppm" in this specification or application refers to weight basis.

[0059] Figure 1 A filament according to an embodiment is shown. Figure 2 A cross section of a filament according to an embodiment is shown. Figure 3 A filament according to another embodiment is shown. Figure 4 A schematic diagram of an apparatus for producing a first biodegradable resin composition according to an embodiment is shown. Figure 5 An apparatus for producing a biodegradable yarn according to an embodiment is shown. Figure 6 A cross section of a spin block according to an embodiment is shown.

[0060] like Figure 1 and 2 As shown, the filament 10 may include a core 12 and a sheath 13 .

[0061] The core 12 may have a shape extending in one direction. The core 12 may have a cylindrical shape extending continuously in one direction.

[0062] The skin portion 13 surrounds the core portion 12. The skin portion 13 may be disposed on the outer peripheral surface of the core portion 12. The skin portion 13 may be in close contact with the outer peripheral surface of the core portion 12. The skin portion 13 may completely cover the outer peripheral surface of the core portion 12.

[0063] The diameter (D) of the core 12 may be about 1 μm to about 100 μm, about 5 μm to about 50 μm, about 10 μm to about 100 μm, about 20 μm to about 100 μm, or about 1 μm to 30 μm.

[0064] The thickness (T) of the leather portion 13 may be about 0.5 μm to about 50 μm, about 2.5 μm to about 25 μm, about 0.5 μm to about 5 μm, about 2.5 μm to about 50 μm, about 0.5 μm to about 2.5 μm, or 5 μm to about 30 μm.

[0065] Alternatively, if Figure 3 As shown, the filament 11 may not have a core-skin structure. The filament 11 may not have a single structure. The filament 11 may have a single-line structure without a boundary. That is, the central part and the outer part of the filament 11 may not have a boundary.

[0066] The filament includes a biodegradable resin composition. That is, the biodegradable yarn according to the embodiment includes a biodegradable resin composition.

[0067] The filament may include a first biodegradable resin composition and a second biodegradable resin composition.

[0068] The core may include a second biodegradable resin composition, and the skin may include a first biodegradable resin composition. The core may include a second biodegradable resin composition as a main component, and the skin may include a first biodegradable resin composition as a main component. The core may be formed of a second biodegradable resin composition, and the skin may be formed of a first biodegradable resin composition.

[0069] The first biodegradable resin composition and the second biodegradable resin composition may have different characteristics. For example, the first biodegradable resin composition may be more viscous than the second biodegradable resin composition. The second biodegradable resin composition may have a greater mechanical strength than the first biodegradable resin composition. In addition, the first biodegradable resin composition may have a higher flexibility than the second biodegradable resin composition. In addition, the first biodegradable resin composition may have a lower crystallinity than the second biodegradable resin composition.

[0070] Therefore, the filament 11 may have improved mechanical strength and improved adhesiveness. In addition, the filament 11 may have improved mechanical strength and improved flexibility.

[0071] Detailed features of the first biodegradable resin composition and the second biodegradable resin composition are described below.

[0072] Optionally, the core may include a first biodegradable resin composition, and the skin may include a second biodegradable resin composition. The core may include a first biodegradable resin composition as a main component, and the skin may include a second biodegradable resin composition as a main component. The core may be made of a first biodegradable resin composition, and the skin may be made of a second biodegradable resin composition.

[0073] Alternatively, the core may include a non-biodegradable resin composition, and the sheath may include a first biodegradable resin composition and / or a second biodegradable resin composition.

[0074] Alternatively, the core may include the first biodegradable resin composition and / or the second biodegradable resin composition, and the sheath may include a non-biodegradable resin composition.

[0075] The non-biodegradable resin composition may include at least one selected from the group consisting of polypropylene, polyethylene, polybutylene terephthalate, polyethylene terephthalate, and polyurethane.

[0076] The core may include a first biodegradable resin composition and a second biodegradable resin composition. The skin may include a first biodegradable resin composition and a second biodegradable resin composition. The core may include a second biodegradable resin composition, and the skin may include a mixture of the first biodegradable resin composition and the second biodegradable resin composition.

[0077] The biodegradable yarn according to the embodiment may include a mixture of a first biodegradable resin composition and a second biodegradable resin composition. The biodegradable yarn according to the embodiment may include a second biodegradable resin composition in an amount of about 50 parts by weight to about 300 parts by weight based on about 100 parts by weight of the first biodegradable resin composition.

[0078] The first biodegradable resin composition includes a first biodegradable resin. The first biodegradable resin composition may include only the first biodegradable resin. The first biodegradable resin composition may include a first biodegradable resin having a content of about 50wt% to about 99.9wt% based on the total weight. The first biodegradable resin composition may include a first biodegradable resin having a content of about 70wt% to about 99.9wt% based on the total weight. The first biodegradable resin composition may include a first biodegradable resin having a content of about 90wt% to about 99.9wt% based on the total weight. The first biodegradable resin composition may include a first biodegradable resin having a content of about 95wt% to about 99.9wt% based on the total weight. The first biodegradable resin composition may include a first biodegradable resin, additional additives, and the like.

[0079] The first biodegradable resin comprises glycol, aromatic dicarboxylic acid and aliphatic dicarboxylic acid.The first biodegradable resin comprises glycol moiety, aromatic dicarboxylic acid moiety and aliphatic dicarboxylic acid moiety.The glycol moiety is derived from glycol, the aromatic dicarboxylic acid moiety is derived from aromatic dicarboxylic acid, and the aliphatic dicarboxylic acid moiety is derived from aliphatic dicarboxylic acid.The first biodegradable resin comprises glycol component, aromatic dicarboxylic acid component and aliphatic dicarboxylic acid component.Similarly, glycol component can be derived from glycol, aromatic dicarboxylic acid component can be derived from aromatic dicarboxylic acid, and aliphatic dicarboxylic acid component can be derived from aliphatic dicarboxylic acid.

[0080] In describing the first biodegradable resin composition, the diol part can be represented as diol. In the first biodegradable resin, the dicarboxylic acid part can be represented as dicarboxylic acid. In addition, the part can be represented as component.

[0081] The diol may be an aliphatic diol. The diol may be at least one selected from the group consisting of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propylene glycol, 2,2-dimethyl-1,3-propylene glycol, 2,2-diethyl-1,3-propylene glycol, 2-ethyl-2-isobutyl-1,3-propylene glycol, 1,2-butylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 2,2,4-trimethyl-1,3-pentanediol, 1,6-hexanediol, 2-ethyl-1,3-hexanediol, 2,4-dimethyl-2-ethyl-1,3-hexanediol, 2,2,4-trimethyl-1,6-hexanediol, 2-methyl-1,8-octanediol, 1,9-nonanediol, 1,10-decanediol and 1,12-octadecanediol and derivatives thereof.

[0082] The diol may be at least one selected from the group consisting of 1,4-butanediol, 1,2-ethylene glycol, 1,3-propylene glycol, diethylene glycol, neopentyl glycol, and derivatives thereof.

[0083] The diol is at least one selected from the group consisting of 1,4-butanediol, 1,2-ethylene glycol, 1,3-propylene glycol, 2,3-butanediol, and derivatives thereof.

[0084] The diol may include 1,4-butanediol or a derivative thereof.

[0085] The aromatic dicarboxylic acid may be at least one selected from the group consisting of phthalic acid, terephthalic acid, isophthalic acid, 1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 1,8-naphthalene dicarboxylic acid, 4,4'-biphenyl dicarboxylic acid, 4,4'-biphenyl ether dicarboxylic acid, anthracene dicarboxylic acid, phenanthrene dicarboxylic acid and derivatives thereof.

[0086] The aromatic dicarboxylic acid may be at least one selected from the group consisting of terephthalic acid, dimethyl terephthalate, 2,6-naphthalene dicarboxylic acid, isophthalic acid, and derivatives thereof.

[0087] The aromatic dicarboxylic acid may include terephthalic acid, dimethyl terephthalate, or a derivative.

[0088] The aliphatic dicarboxylic acid may be at least one selected from the group consisting of oxalic acid, malonic acid, succinic acid, maleic acid, fumaric acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, and derivatives thereof.

[0089] The aliphatic dicarboxylic acid may be at least one selected from the group consisting of adipic acid, succinic acid, sebacic acid, and derivatives thereof.

[0090] The aliphatic dicarboxylic acid may include adipic acid or a derivative thereof.

[0091] In the first biodegradable resin, the molar ratio of the total glycol portion (including glycol) to the total dicarboxylic acid portion (including aromatic dicarboxylic acid and aliphatic dicarboxylic acid) may be about 1:0.9 to about 1:1.1. The molar ratio of the total glycol portion to the total dicarboxylic acid portion may be about 1:0.95 to about 1:1.05.

[0092] In the first biodegradable resin, the molar ratio of the aromatic dicarboxylic acid moiety to the aliphatic dicarboxylic acid moiety may be about 3:7 to about 7:3. In the first biodegradable resin, the molar ratio of the aromatic dicarboxylic acid moiety to the aliphatic dicarboxylic acid moiety may be about 3.3:6.7 to about 6.7:3.3. In the first biodegradable resin, the molar ratio of the aromatic dicarboxylic acid moiety to the aliphatic dicarboxylic acid moiety may be about 4:6 to about 6:4. In the first biodegradable resin, the molar ratio of the aromatic dicarboxylic acid moiety to the aliphatic dicarboxylic acid moiety may be about 4.2:5.8 to about 5:5.

[0093] The first biodegradable resin may include a diol portion derived from 1,4-butanediol in an amount of about 90 mol% or more based on the total diols. The first biodegradable resin may include a diol portion derived from 1,4-butanediol in an amount of about 95 mol% or more based on the total diols. The first biodegradable resin may include a diol portion derived from 1,4-butanediol in an amount of about 98 mol% or more based on the total diols.

[0094] The first biodegradable resin may include an aromatic dicarboxylic acid portion derived from terephthalic acid or dimethyl terephthalate at a content of about 30 mol % to about 70 mol % based on the total dicarboxylic acid. The first biodegradable resin may include an aromatic dicarboxylic acid portion derived from terephthalic acid or dimethyl terephthalate at a content of about 35 mol % to about 65 mol % based on the total dicarboxylic acid. The first biodegradable resin may include a dicarboxylic acid portion derived from terephthalic acid or dimethyl terephthalate at a content of about 40 mol % to about 60 mol % based on the total dicarboxylic acid. The first biodegradable resin may include an aromatic dicarboxylic acid portion derived from terephthalic acid or dimethyl terephthalate at a content of about 43 mol % to about 55 mol % based on the total dicarboxylic acid.

[0095] The first biodegradable resin may include an aliphatic dicarboxylic acid portion derived from adipic acid in an amount of about 30 mol% to about 70 mol% based on the total dicarboxylic acids. The first biodegradable resin may include an aliphatic dicarboxylic acid portion derived from adipic acid in an amount of about 35 mol% to about 65 mol% based on the total dicarboxylic acids. The first biodegradable resin may include an aliphatic dicarboxylic acid portion derived from adipic acid in an amount of about 40 mol% to about 60 mol% based on the total dicarboxylic acids. The first biodegradable resin may include an aliphatic dicarboxylic acid portion derived from adipic acid in an amount of about 47 mol% to about 57 mol% based on the total dicarboxylic acids.

[0096] In addition, the first biodegradable resin may include a first block and a second block. The first biodegradable resin may have a molecular structure in which the first block and the second block are alternately combined.

[0097] The first block may include a diol portion and an aromatic dicarboxylic acid portion. The first block may be formed by an esterification reaction of a diol and an aromatic dicarboxylic acid. The first block may include only a diol portion and an aromatic dicarboxylic acid portion. The first block may include only repeating units formed by an esterification reaction of a diol and an aromatic dicarboxylic acid. That is, the first block may mean the sum of repeating units of a diol and an aromatic dicarboxylic acid before being combined with an aliphatic dicarboxylic acid.

[0098] The second block may include a diol portion and an aliphatic dicarboxylic acid portion. The second block may be formed by an esterification reaction of a diol and an aliphatic dicarboxylic acid. The second block may include only a diol portion and an aliphatic dicarboxylic acid portion. The second block may include only repeating units formed by an esterification reaction of a diol and an aliphatic dicarboxylic acid. That is, the second block may mean the sum of repeating units of a diol and an aliphatic dicarboxylic acid before being combined with an aromatic dicarboxylic acid.

[0099] In the first biodegradable resin, the ratio (X / Y) of the number of the first block (X) to the number of the second block (Y) may be about 0.5 to about 1.5, about 0.6 to about 1.4, about 0.7 to about 1.3, about 0.75 to about 1.2, or about 0.8 to 1.1. The number of the first block may be less than the number of the second block.

[0100] The number of first blocks can be from about 30 to about 300, from about 40 to about 250, from about 50 to about 220, from about 60 to about 200, from about 70 to about 200, or from about 75 to about 200.

[0101] The number of the first blocks may vary according to the content of the aromatic dicarboxylic acid, the molecular weight of the first biodegradable resin, and the polymerization process described below. That is, as the molar ratio of the aromatic dicarboxylic acid increases and the molecular weight of the first biodegradable resin increases, the number of the first blocks may increase.

[0102] The number of second blocks can be from about 30 to about 300, from 40 to about 250, from about 50 to about 220, from about 60 to about 200, from about 70 to about 200, or from about 75 to about 200.

[0103] The number of the second blocks may vary according to the content of the aliphatic dicarboxylic acid, the molecular weight of the first biodegradable resin, and the polymerization process described below. That is, as the molar ratio of the aliphatic dicarboxylic acid increases and the molecular weight of the first biodegradable resin increases, the number of the second blocks may increase.

[0104] When the first biodegradable resin includes the first block and the second block within the above range, the first biodegradable resin composition can have appropriate mechanical strength and appropriate biodegradability. In addition, when the first biodegradable resin includes the first block and the second block within the above range, the first biodegradable resin composition can have improved hardness and improved flexibility. Therefore, the first biodegradable resin composition can be easily used to produce injection molded products. In addition, when the first biodegradable resin includes the first block and the second block within the above range, the first biodegradable resin composition can have appropriate durability and appropriate biodegradability to ultraviolet rays, etc.

[0105] The first block can be represented by the following Formula 1:

[0106] [Formula 1]

[0107]

[0108] wherein R1 is a substituted or unsubstituted arylene group having 6 to 20 carbon atoms, R2 is a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms, and m is 1 to 20.

[0109] R1 may be a substituted or unsubstituted phenylene group, and R2 may be a butene group.

[0110] The second block can be represented by the following Formula 2:

[0111] [Formula 2]

[0112]

[0113] wherein R3 and R4 are each independently a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms, and n is 1 to 20.

[0114] R3 and R4 may be butene groups.

[0115] The first biodegradable resin may have a structure in which the first block and the second block are alternately combined with each other. The first biodegradable resin may be represented by the following Formula 3:

[0116] [Formula 3]

[0117]

[0118] wherein R1 is a substituted or unsubstituted arylene group having 6 to 20 carbon atoms, R2 is a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms, and m is 1 to 20. In addition, R3 and R4 are each independently a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms, and n is 1 to 20.

[0119] The diol moiety may include a moiety of 1,4-butanediol or a derivative thereof, the aromatic dicarboxylic acid moiety may include a moiety of terephthalic acid or a derivative thereof, and the aliphatic dicarboxylic acid moiety may include a moiety of adipic acid or a derivative thereof.

[0120] For example, the first biodegradable resin may include a first block including a portion of 1,4-butanediol or a derivative thereof and a portion of terephthalic acid or a derivative thereof.

[0121] Alternatively, the first biodegradable resin may include a first block including a portion of 1,4-butanediol or a derivative thereof and a portion of dimethyl terephthalate or a derivative thereof.

[0122] The first biodegradable resin may include a second block including a portion of 1,4-butanediol or a derivative thereof and a portion of adipic acid or a derivative thereof.

[0123] Alternatively, the first biodegradable resin may include a second block including a portion of 1,4-butanediol or a derivative thereof and a portion of succinic acid or a derivative thereof.

[0124] The first biodegradable resin may include a first block including a portion of 1,4-butanediol or a derivative thereof and a portion of terephthalic acid or a derivative thereof, and a second block including a portion of 1,4-butanediol or a derivative thereof and a portion of adipic acid or a derivative thereof.

[0125] The first block may be represented by the following Formula 4, and the second block may be represented by the following Formula 5:

[0126] [Formula 4]

[0127]

[0128] Wherein m is 1 to 20.

[0129] [Formula 5]

[0130]

[0131] Wherein n is 1 to 20.

[0132] The first biodegradable resin may be represented by the following Formula 6:

[0133] [Formula 6]

[0134]

[0135] wherein m is 1 to 20, and n is 1 to 20.

[0136] When the first block and the second block satisfy the above configuration, it may be more advantageous to provide a biodegradable polyester sheet, film or shaped article having excellent biodegradability and water decomposability and improved physical properties.

[0137] In addition, when the first biodegradable resin includes the first block and the second block within the above range, the first biodegradable resin composition may have appropriate mechanical properties and appropriate UV resistance.

[0138] Since the first block and the second block have the above characteristics, the mechanical properties of the first biodegradable resin composition can be improved.

[0139] Since the first block and the second block have the above characteristics, the first biodegradable resin composition can have appropriate UV resistance.

[0140] Since the first block and the second block have the above characteristics, the first biodegradable resin composition can have an appropriate biodegradation rate.

[0141] Since the first block and the second block have the above-mentioned characteristics, the first biodegradable resin composition can have an appropriate hydrolysis rate.

[0142] The first biodegradable resin may further include a branching agent. The branching agent may include trivalent or higher alcohols and / or trihydroxy or higher hydroxy carboxylic acids. The branching agent may react with glycols, aromatic dicarboxylic acids, and aliphatic dicarboxylic acids. Therefore, the branching agent may be included as part of the molecular structure of the first biodegradable resin.

[0143] The trivalent or higher-valent alcohol may be at least one selected from the group consisting of glycerin, pentaerythritol, and trimethylolpropane.

[0144] The trihydroxy or higher hydroxy carboxylic acid may be at least one selected from the group consisting of methanetricarboxylic acid, ethanetricarboxylic acid, citric acid, benzene-1,3,5-tricarboxylic acid, 5-sulfo-1,2,4-benzenetricarboxylic acid, ethane-1,1,2,2-tetracarboxylic acid, propane-1,1,2,3-tetracarboxylic acid, butane-1,2,3,4-tetracarboxylic acid, cyclopentane-1,2,3,4-tetracarboxylic acid, and benzene-1,2,4,5-tetracarboxylic acid.

[0145] The first biodegradable resin may include about 0.1 wt% to about 5 wt% of a branching agent, based on the total weight of the first biodegradable resin. The first biodegradable resin may include about 0.1 wt% to about 3 wt% of a branching agent, based on the total weight of the first biodegradable resin. The first biodegradable resin may include about 0.1 wt% to about 1 wt% of a branching agent, based on the total weight of the first biodegradable resin.

[0146] Since the first biodegradable resin includes the branching agent within the above range, the first biodegradable resin composition may have appropriate mechanical properties and appropriate biodegradability.

[0147] Based on the total weight of the first biodegradable resin composition, the biodegradable resin may be included in an amount of about 30 wt % or more, about 50 wt % or more, about 70 wt % or more, about 80 wt % or more, about 90 wt % or more, about 95 wt % or more, or about 99 wt % or more. Based on the total weight of the first biodegradable resin composition, the maximum content of the biodegradable resin in the first biodegradable resin composition may be about 100 wt %.

[0148] The first biodegradable resin composition may further include a crystallization temperature regulator. The crystallization temperature regulator can control the crystallization temperature of the first biodegradable resin composition. The crystallization temperature regulator can be a reinforcing material that can improve the mechanical properties of the first biodegradable resin composition and the film or molded product produced therewith. In addition, the crystallization temperature regulator can control the deformation characteristics of the first biodegradable resin composition by ultraviolet light. In addition, the crystallization temperature regulator can control the hydrolysis characteristics of the first biodegradable resin composition. In addition, the crystallization temperature regulator can control the biodegradability of the first biodegradable resin according to the embodiment.

[0149] The crystallization temperature regulator can be a fiber derived from biomass. The crystallization temperature regulator can be a fiber made of organic material. That is, the crystallization temperature regulator can be a fiber-based crystallization temperature regulator. The fiber-based crystallization temperature regulator can be nanocellulose.

[0150] The nanocellulose may be one or more selected from the group consisting of nanocrystalline cellulose, cellulose nanofibers, microfibrillated cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, cellulose acetate, methyl cellulose, ethyl cellulose, propyl cellulose, butyl cellulose, pentyl cellulose, hexyl cellulose and cyclohexyl cellulose.

[0151] Nanocellulose may include ionic metals. Nanocrystalline cellulose may include alkali metals. Nanocellulose may include sodium. In addition, nanocellulose may include sulfates. Nanocellulose may include carboxylates. Nanocellulose may be sodium bisulfate of cellulose.

[0152] Nanocellulose can be represented by the following formula 7:

[0153] [Formula 7]

[0154] (C6H 10 O5) x SO3Na] y

[0155] wherein x is 1 to 35, and y is 1 to 10. x may be 15 to 35, and y may be 1 to 10.

[0156] The specific surface area of ​​nanocellulose can be about 200 m 2 / g to about 600m 2 / g, or the specific surface area can be about 250m 2 / g to about 500m 2 / g.

[0157] The weight average molecular weight of the nanocellulose may be about 10,000 g / mol to about 40,000 g / mol or about 11,000 g / mol to about 35,000 g / mol.

[0158] The moisture content of the nanocellulose may be about 2 wt % to about 8 wt %. The moisture content of the nanocellulose may be about 4 wt % to about 6 wt %.

[0159] The average diameter of nanocellulose can be from about 0.5 nm to about 20 nm. The average diameter of nanocellulose can be from about 1 nm to about 15 nm. The average diameter of nanocellulose can be from about 1.5 nm to about 12 nm. The average diameter of nanocellulose can be from about 2 nm to about 11 nm.

[0160] The average length of nanocellulose can be from about 20nm to about 300nm. The average length of nanocellulose can be from about 30nm to about 500nm. The average length of nanocellulose can be from about 30nm to about 180nm. The average length of nanocellulose can be from about 35nm to about 150nm. The average length of nanocellulose can be from about 100nm to about 300nm.

[0161] The aspect ratio (average length / average diameter) of the nanocellulose may be about 10 to about 50. The aspect ratio of the nanocellulose may be about 20 to about 40. The aspect ratio of the nanocellulose may be about 25 to about 35.

[0162] Since the nanocellulose has the above-mentioned average diameter, average length, and aspect ratio, the mechanical properties of the biodegradable resin composition according to the embodiment may be effectively enhanced.

[0163] In particular, when the diameter and length of nanocellulose satisfy the above ranges, the biodegradability and characteristics of the first biodegradable resin or the biodegradable polyester sheet, film, and molded article obtained using the first biodegradable resin can be further improved.

[0164] The diameter and length of nanocellulose can be measured by atomic force microscopy when dispersed in water.

[0165] Based on the total amount of nanocellulose, the content of sulfur in the nanocellulose can be about 0.1 wt % to about 1.2 wt %. Based on the total amount of nanocellulose, the content of sulfur in the nanocellulose can be about 0.75 wt % to about 1.1 wt %. Based on the total amount of nanocellulose, the content of sulfur in the nanocellulose can be about 0.5 wt % to about 1.5 wt %.

[0166] The sulfur content in nanocellulose can be measured according to ASTM D2622.

[0167] The nanocellulose may include a surface treatment agent. The surface treatment agent may include at least one selected from the group consisting of sulfates and carboxylates. That is, the nanocellulose may be surface treated with sulfates or carboxylates.

[0168] The pH of the nanocellulose may be between 5 and 7. The pH of the nanocellulose may be between 6 and 7. The pH of the nanocellulose may be between 5 and 8.

[0169] The zeta potential of nanocellulose can be about -50 mV to about -25 mV. The zeta potential of nanocellulose can be about -45 mV to about -30 mV. The zeta potential of nanocellulose can be about -60 mV to about -25 mV. The zeta potential of nanocellulose can be about -55 mV to about -30 mV.

[0170] The zeta potential of cellulose can be measured using a zeta potential instrument (eg, Zetasizer Nano ZS, Malvern).

[0171] Based on 100 parts by weight of the first biodegradable resin, nanocellulose may be included in the first biodegradable resin composition at a content of about 0.01 parts by weight to about 2 parts by weight. Based on 100 parts by weight of the first biodegradable resin, nanocellulose may be included in the first biodegradable resin composition at a content of about 0.03 parts by weight to about 1.5 parts by weight. Based on 100 parts by weight of the first biodegradable resin, nanocellulose may be included in the first biodegradable resin composition at a content of about 0.04 parts by weight to about 1.2 parts by weight. Based on 100 parts by weight of the first biodegradable resin, nanocellulose may be included in the first biodegradable resin composition at a content of about 0.05 parts by weight to about 1 part by weight.

[0172] Since nanocellulose has the above characteristics, it can be uniformly dispersed in the first biodegradable resin composition.

[0173] Since nanocellulose has the above characteristics, it can improve the mechanical properties of the first biodegradable resin composition.

[0174] In addition, nanocellulose can be used as a crystal nucleating agent to improve the crystallization rate of the first biodegradable resin composition. Therefore, nanocellulose can increase the crystallization temperature of the first biodegradable resin composition.

[0175] Since nanocellulose has the above characteristics, the first biodegradable resin composition can have appropriate UV resistance.

[0176] Since nanocellulose has the above characteristics, the first biodegradable resin composition can have an appropriate biodegradation rate.

[0177] Since nanocellulose has the above characteristics, the first biodegradable resin composition can have an appropriate hydrolysis rate.

[0178] The first biodegradable resin composition may further include a germanium-based catalyst or a titanium-based catalyst. Germanium-based catalysts and titanium-based catalysts may be added during the production of the first biodegradable resin composition. Germanium-based catalysts and titanium-based catalysts may affect the crystallinity of the first biodegradable resin composition. In addition, germanium-based catalysts and titanium-based catalysts are described in detail below.

[0179] The first biodegradable resin composition may include a metal salt.

[0180] The first biodegradable resin composition may include the metal salt in an amount of about 0.1 ppm to about 1000 ppm, about 1 ppm to about 500 ppm, about 1 ppm to about 100 ppm, or about 1 ppm to about 50 ppm, based on the total weight of the first biodegradable resin composition.

[0181] The metal salt may be at least one selected from the group consisting of nitrates, sulfates, hydrochlorides, carboxylates, etc. The metal salt may be at least one selected from the group consisting of titanium salts, silicon salts, sodium salts, calcium salts, potassium salts, magnesium salts, copper salts, iron salts, aluminum salts, silver salts, etc. The metal salt may be at least one selected from the group consisting of magnesium acetate, calcium acetate, potassium acetate, copper nitrate, silver nitrate, sodium nitrate, etc.

[0182] The metal salt may include one or more selected from the group consisting of iron (Fe), magnesium (Mg), nickel (Ni), cobalt (Co), copper (Cu), palladium (Pd), zinc (Zn), vanadium (V), titanium (Ti), indium (In), manganese (Mn), silicon (Si) and tin (Sn).

[0183] Furthermore, the metal salt may be selected from the group consisting of acetate, nitrate, nitride, sulfide, sulfate, sulfoxide, hydroxide, hydrate, chloride, chlorinate, and bromide.

[0184] Since the first biodegradable resin composition includes the metal salt within the above range, the hydrolysis rate and the biodegradation rate may be appropriately controlled.

[0185] The first biodegradable resin composition may further include an anti-hydrolysis agent.

[0186] The anti-hydrolysis agent may be at least one selected from silicon-based compounds such as silane, silazane, and siloxane.

[0187] The anti-hydrolysis agent may include alkoxysilane. The anti-hydrolysis agent may include trimethoxysilane and / or triethoxysilane. The anti-hydrolysis agent may include alkoxysilane containing epoxy groups. The anti-hydrolysis agent may include at least one selected from the group consisting of: 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane and 3-glycidoxypropyltriethoxysilane.

[0188] In the first biodegradable resin composition, the anti-hydrolysis agent may be included in an amount of about 1 ppm to about 10000 ppm, in an amount of about 1 ppm to about 1000 ppm, in an amount of about 5 ppm to about 500 ppm, or in an amount of about 10 ppm to about 300 ppm.

[0189] The anti-hydrolysis agent may be bonded to the first biodegradable resin. The anti-hydrolysis agent may be chemically bonded to the first biodegradable resin. The anti-hydrolysis agent may be chemically bonded to a polymer contained in the first biodegradable resin. The anti-hydrolysis agent may be coupled to a polymer contained in the first biodegradable resin.

[0190] Since the first biodegradable resin composition includes the anti-hydrolysis agent within the above range, it can have appropriate anti-hydrolysis characteristics. In particular, since the first biodegradable resin according to the embodiment includes the anti-hydrolysis agent within the above range, it can have appropriate initial anti-hydrolysis characteristics and improved biodegradability.

[0191] The first biodegradable resin composition may further include a chain extender.

[0192] The chain extender may include an isocyanate.

[0193] The chain extender may be at least one selected from the group consisting of monofunctional isocyanate and polyfunctional isocyanate.

[0194] The chain extender may be at least one selected from the group consisting of toluene 2,4-diisocyanate, toluene 2,6-diisocyanate, diphenylmethane 4,4′-diisocyanate and 2,4′-diisocyanate, naphthalene 1,5-diisocyanate, xylylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, isophorone diisocyanate, and methylenebis(4-isocyanocyclohexane).

[0195] The chain extender may include a triisocyanate.The chain extender may include tris(4-isocyanatophenyl)methane.

[0196] The chain extender may include an acrylic polymer. The acrylic polymer may include an acrylic group. The acrylic group may be bonded to the main chain as a side chain. The acrylic polymer may include an epoxy group. The epoxy group may be bonded to the main chain as a side chain.

[0197] The chain extender may include a styrene-based copolymer.The chain extender may include styrene glycidyl acrylate.

[0198] The chain extender may be chemically bonded to the first biodegradable resin. The chain extender may be chemically bonded to a polymer contained in the first biodegradable resin. The chain extender may be bonded to a terminal of a polymer contained in the first biodegradable resin. In addition, the chain extender may be bonded to the terminals of three polymers contained in the first biodegradable resin.

[0199] In the first biodegradable resin composition, the chain extender may be included in an amount of about 0.1 wt % to about 10 wt %, in an amount of about 0.2 wt % to about 8 wt %, or in an amount of about 0.3 wt % to about 7 wt %.

[0200] When the first biodegradable resin composition includes the chain extender within the above range, it may have appropriate hydrolysis resistance and appropriate biodegradability.

[0201] In addition, the chain extender can couple the polymer contained in the first biodegradable resin, so the proportion of the high molecular weight polymer in the first biodegradable resin composition can be increased. Therefore, the mechanical properties of the first biodegradable resin composition can be improved.

[0202] The first biodegradable resin composition may include a thermal stabilizer. The thermal stabilizer may be a phosphorus-based thermal stabilizer.

[0203] The heat stabilizer may be at least one selected from the group consisting of: an amine-based high temperature heat stabilizer such as tetraethylenepentamine, triethyl phosphoacetate, phosphoric acid, phosphorous acid, polyphosphoric acid, trimethyl phosphate (TMP), triethyl phosphate, trimethylphosphine, triphenylphosphine, and the like.

[0204] Furthermore, the heat stabilizer may be an antioxidant having an anti-oxidation function.

[0205] Based on the gross weight of the first biodegradable resin, the content of the heat stabilizer may be about 3000ppm. Based on the gross weight of the first biodegradable resin, the content of the heat stabilizer may be, for example, 10ppm to 3,000ppm, 20ppm to 2,000ppm, 20ppm to 1,500ppm or 20ppm to 200ppm. When the content of the heat stabilizer meets these ranges, the polymer degradation due to high temperature during the reaction process may be controlled so that the terminal groups of the polymer may be reduced and the color may be improved. In addition, the heat stabilizer may inhibit the activation of titanium-based catalysts, etc., to control the reaction rate.

[0206] The first biodegradable resin composition may include an elongation improver. Examples of the elongation improver include oils such as paraffin oil, naphthenic oil or aromatic oil, or adipates such as dibutyl adipate, diethylhexyl adipate, dioctyl adipate or diisopropyl adipate.

[0207] The elongation improving agent may be included in the first biodegradable resin composition in an amount of about 0.001 parts by weight to about 1 part by weight, based on 100 parts by weight of the first biodegradable resin. The elongation improving agent may be included in the first biodegradable resin composition in an amount of about 0.01 parts by weight to about 1 part by weight, based on 100 parts by weight of the first biodegradable resin.

[0208] Since the elongation improving agent is included within the above range, the first biodegradable resin composition may have improved mechanical properties.

[0209] The first biodegradable resin composition may include an inorganic filler. The inorganic filler may be at least one selected from the group consisting of calcium sulfate, barium sulfate, talc, talc powder, bentonite, kaolin, chalk powder, calcium carbonate, graphite, gypsum, conductive carbon black, calcium chloride, iron oxide, aluminum oxide, potassium oxide, dolomite, silicon dioxide, wollastonite, titanium dioxide, silicate, mica, glass fiber, mineral fiber, etc.

[0210] For inorganic fillers, the cumulative 50% particle size (D 50 ) can be about 100 μm or less, about 85 μm or less, about 70 μm or less, about 50 μm or less, about 25 μm or less, about 10 μm or less, about 5 μm or less, about 3 μm or less or about 1 μm or less.

[0211] In addition, the specific surface area of ​​the inorganic filler can be about 100 m 2 / g or more. For example, the specific surface area of ​​the inorganic filler can be about 100m 2 / g or greater, about 105m 2 / g or greater or about 110m 2 / g or greater.

[0212] The inorganic filler may be included in the first biodegradable resin composition in an amount of about 3 parts by weight to about 50 parts by weight, based on 100 parts by weight of the first biodegradable resin. The inorganic filler may be included in the first biodegradable resin composition in an amount of about 5 parts by weight to about 30 parts by weight, based on 100 parts by weight of the first biodegradable resin.

[0213] The inorganic filler may be included in an amount of about 3,000 ppm or less based on the total weight of the first biodegradable resin composition. For example, the inorganic filler may be included in an amount of about 3,000 ppm or less, about 1,500 ppm or less, about 1,200 ppm or less, about 800 ppm or less, about 600 ppm or less, about 50 ppm or more, about 100 ppm or more, about 130 ppm or more, about 150 ppm or more, or about 180 ppm or more based on the total weight of the first biodegradable resin composition.

[0214] Since the first biodegradable resin composition includes the inorganic filler within the above content range, the first biodegradable resin composition may have mechanical properties such as appropriate UV resistance, an appropriate biodegradation rate, and an appropriate hydrolysis rate.

[0215] In addition, the number of carboxyl terminal groups in the first biodegradable resin composition may be about 20 eq / ton to about 60 eq / ton. In the first biodegradable resin composition, the number of carboxyl terminal groups may be about 30 eq / ton to about 60 eq / ton. In the first biodegradable resin composition, the number of carboxyl terminal groups may be about 30 eq / ton to about 50 eq / ton.

[0216] When the number of carboxyl terminal groups is controlled within the above range and the first biodegradable resin composition is spun to form a yarn, degradation can be prevented and improved mechanical properties can be achieved. When the number of carboxyl terminal groups is within the above range, the yarns produced with the first biodegradable resin composition can be easily fused with each other. In addition, when the number of carboxyl terminal groups is within the above range, burrs can be prevented from occurring in the yarn produced with the first biodegradable resin composition.

[0217] The process of preparing the first biodegradable resin composition is as follows.

[0218] refer to Figure 4 The apparatus for preparing the first biodegradable resin includes a slurry agitator 100 , an esterification supply line 200 , a polycondensation supply line 300 , a post-processor 400 , a first recoverer 510 , and a second recoverer 520 .

[0219] The method of preparing a first biodegradable resin includes preparing a first raw material composition including a diol and an aromatic dicarboxylic acid.

[0220] The first raw material composition may be prepared as a slurry including the diol and the aromatic dicarboxylic acid.

[0221] The step of preparing the slurry includes a mixing and treating step of mixing and treating the diol and the aromatic dicarboxylic acid. That is, the step of preparing the slurry may be a pretreatment step before the esterification reaction, and may be a step of mixing the diol and the aromatic dicarboxylic acid and slurrying them.

[0222] The slurry temperature of the diol and the aromatic dicarboxylic acid may be higher than the melting point of the diol by about 5° C. to about 15° C. For example, when the diol is 1,4-butanediol, the temperature of the slurry may be about 35° C. to about 45° C.

[0223] The diol and the aromatic dicarboxylic acid are fed into the slurry agitator 100 and agitated therein to generate slurry.

[0224] By mixing and pre-treating the diol and the aromatic dicarboxylic acid to form a slurry, the diol and the aromatic dicarboxylic acid can be uniformly reacted, and this can effectively rapidly perform the esterification reaction, thereby improving the reaction efficiency.

[0225] In particular, when an aromatic dicarboxylic acid (such as terephthalic acid) has complete crystallinity and is in powder form, its solubility in glycol is extremely low, making it difficult to undergo a homogeneous reaction. Therefore, the pretreatment process of slurrying can play a very important role in providing the first biodegradable resin, sheet, film and molded article with excellent physical properties according to an embodiment of the present invention and improving reaction efficiency.

[0226] When the aromatic dicarboxylic acid is terephthalic acid, terephthalic acid has perfect crystallinity and is a white crystal that sublimes at about 300°C at normal pressure with no melting point. The solubility of aromatic dicarboxylic acids in diols is extremely low, making it difficult to react homogeneously. Therefore, if a pretreatment process is performed before the esterification reaction, a uniform reaction can be induced by increasing the surface area for reaction with diols within the solid matrix of terephthalic acid.

[0227] In addition, when the aromatic dicarboxylic acid is dimethyl terephthalate, dimethyl terephthalate may be reacted with diol in a molten state at about 142° C. to 170° C. through a pretreatment process. Therefore, the esterification reaction may be performed faster and more efficiently.

[0228] Meanwhile, in the pretreatment step of preparing the slurry, the structure and characteristics of the first biodegradable resin may vary according to the particle size, particle size distribution, pretreatment reaction conditions, and the like of the aromatic dicarboxylic acid.

[0229] For example, the aromatic dicarboxylic acid may include terephthalic acid, and in the particle size distribution (PSD), the average particle diameter (D50) of the terephthalic acid may be 10 μm to 400 μm, measured by a particle size analyzer Microtrac S3500, and may have a standard deviation of 100 or less for the average particle diameter (D50). Standard deviation means the square root of the variance. The average particle diameter (D50) of terephthalic acid may be, for example, 20 μm to 200 μm, for example, 30 μm to 200 μm, or for example, 100 μm to 160 μm. When the average particle diameter (D50) of terephthalic acid meets these ranges, it may be more advantageous in terms of improving solubility and reaction rate in diols.

[0230] During the pretreatment process, the diol and the aromatic dicarboxylic acid may be mixed and fed into a slurry agitator 100 (tank).

[0231] For example, the slurry agitator 100 may have an anchor type bottom and a height of 20 mm or more from the agitator, and may be equipped with 3 or more spinning blades, which may be more advantageous for achieving an effective agitation effect.

[0232] For example, the height from the slurry agitator 100 may be 20 mm or higher, that is, the supply line and the bottom of the agitator may be almost connected to each other. In this case, slurry can be obtained without precipitation. If the shape, form and spinning blades of the agitator do not meet the above conditions, when the diol and the aromatic dicarboxylic acid are initially mixed, the aromatic dicarboxylic acid may be deposited to the bottom. In this case, phase separation may occur.

[0233] The pretreatment process of preparing the slurry may include the steps of mixing the diol and the aromatic dicarboxylic acid and stirring at about 30° C. to about 100° C. at about 50 rpm to about 200 rpm for 10 minutes or more, for example, 10 minutes to 200 minutes.

[0234] The diol may be added all at once or in divided doses. For example, the diol may be added separately when mixed with the aromatic dicarboxylic acid and after mixed with the aliphatic dicarboxylic acid.

[0235] The aromatic dicarboxylic acid may have the above-mentioned characteristics.

[0236] In the pretreatment step of preparing the slurry, the molar ratio of diol to aromatic dicarboxylic acid may be about 0.8:1 to about 2:1, about 1.1:1 to about 1.5:1, about 1.2:1 to about 1.8:1, or about 1.25:1 to about 1.6:1.

[0237] When the added amount of the diol is larger than that of the aromatic dicarboxylic acid, the aromatic dicarboxylic acid can be easily dispersed.

[0238] Furthermore, additives may be added to the slurry.Nanocellulose and / or metal salts may be added to the slurry in the form of a dispersion or a solution.

[0239] The method for preparing the first biodegradable resin composition is to obtain a prepolymer by esterifying the slurry obtained by mixing and pre-treating diol and aromatic dicarboxylic acid, and performing a polycondensation reaction of the prepolymer. Therefore, the structure and physical properties of the desired first biodegradable resin according to an embodiment of the present invention can be effectively achieved.

[0240] The first raw material composition may have a viscosity of about 300 cP to about 1000 cP at about 35° C., or a viscosity of about 400 cP to about 900 cP.

[0241] Since the viscosity of the first raw material composition is within the above range, the esterification reaction can be efficiently performed.

[0242] The method for preparing the first biodegradable resin composition includes the step of preparing a second raw material composition (including an aliphatic dicarboxylic acid). The second raw material composition may include a diol and an aliphatic dicarboxylic acid.

[0243] In the second feedstock composition, the molar ratio of the diol to the aliphatic dicarboxylic acid is from about 1.2:1 to about 1.6:1 or from about 1.25:1 to about 1.5:1.

[0244] In addition, the second raw material composition may have a viscosity of about 300 cP to about 1000 cP at about 35° C., or a viscosity of about 500 cP to about 1000 cP.

[0245] Since the molar ratio and viscosity of the second raw material composition are within the above ranges, the esterification reaction can be efficiently performed.

[0246] The method of preparing the first biodegradable resin may include the step of esterifying the first raw material composition and the second raw material composition to prepare a prepolymer. The first raw material composition and the second raw material composition may react in an ester supply line.

[0247] In the esterification reaction, the reaction time can be shortened by using the first raw material composition and the second raw material composition. For example, the slurry obtained in the pretreatment step can shorten the reaction time of the esterification and the reaction time of the polycondensation described below.

[0248] The esterification reaction may be performed at least once.

[0249] In an embodiment, the esterification reaction may be performed batchwise after the second raw material composition is added to the first raw material composition. That is, the first raw material composition may be fed into the esterification supply line, and the second raw material composition may be fed into the esterification supply line to perform the esterification reaction.

[0250] The second raw material composition may be added to the first raw material composition in the form of a slurry.

[0251] The esterification reaction may be carried out at a temperature of about 250° C. or less for about 0.5 to about 6 hours. In particular, the esterification reaction may be carried out at about 180° C. to about 250° C., about 185° C. to about 240° C., or about 200° to about 240° C. under normal pressure or reduced pressure until water as a byproduct theoretically reaches 95%. For example, the esterification reaction may be carried out for 0.5 to 5.5 hours, 0.5 to 4.5 hours, or 2 to 5 hours, but the present invention is not limited thereto.

[0252] In the esterification reaction, the total mole number of the added diol may be about 1.0 to about 1.8 or about 1.1 to about 1.6 compared to the total mole number of the aromatic dicarboxylic acid and the aliphatic dicarboxylic acid.

[0253] In addition, the temperature of the second raw material composition (including the diol and the aliphatic dicarboxylic acid) may be about 5° C. to about 15° C. higher than the melting point of the diol.

[0254] Furthermore, various additives such as nanocellulose may be added to the slurry of diol and aliphatic dicarboxylic acid.

[0255] In an embodiment, the first esterification reaction can be carried out after the first raw material composition is fed to the esterification supply pipeline. In addition, after the first esterification, the second raw material composition can be fed to the ester supply pipeline, and the product of the first esterification can be used for the second esterification.

[0256] The first esterification may be performed at a temperature of 250° C. or less for 0.25 to 4 hours. In particular, the first esterification reaction may be performed at 180° C. to 250° C., 185° C. to 240° C., or 200° to 240° C. under normal pressure or reduced pressure until water as a byproduct theoretically reaches 95%. For example, the first esterification reaction may be performed for 0.25 to 4 hours, 0.25 to 3.5 hours, or 1.5 to 3 hours, but the present invention is not limited thereto.

[0257] The second esterification may be performed at a temperature of about 250° C. or less for 0.25 to 3.5 hours. In particular, the second esterification reaction may be performed at 180° C. to 250° C., 185° C. to 240° C., or 200° to 240° C. under normal pressure or reduced pressure until water as a byproduct theoretically reaches 95%. For example, the second esterification reaction may be performed for 0.5 to 3 hours, 1 to 2.5 hours, or 1.5 to 3 hours, but the present invention is not limited thereto.

[0258] In the first esterification and the second esterification, the reaction temperature and the reaction time can be controlled respectively to adjust the quantity ratio of the first block to the second block, etc. In addition, when the esterification is divided into the first esterification and the second esterification, the entire esterification can be accurately controlled. Therefore, when the esterification reaction is performed separately, the reaction stability and reaction uniformity of the esterification can be improved.

[0259] The number average molecular weight of prepolymer can be about 500 to about 10000g / mol. For example, the number average molecular weight of prepolymer can be about 500 to about 8500g / mol, about 500 to about 8000g / mol, about 500 to about 7000g / mol, about 500g / mol to about 5000g / mol or about 1500g / mol to about 4000g / mol. When the number average molecular weight of prepolymer meets these scopes, the molecular weight of polymer in polycondensation reaction can be effectively increased.

[0260] The number average molecular weight can be measured using gel permeation chromatography (GPC). In particular, data obtained by gel permeation chromatography includes several items such as Mn, Mw, and Mp, but the molecular weight can be measured based on the number average molecular weight (Mn).

[0261] Crystallization temperature regulator, branching agent and / or metal salt can be added with slurry before esterification. Crystallization temperature regulator, branching agent and / or metal salt can be fed to esterification supply line 200 in the middle of esterification. Crystallization temperature regulator, branching agent and / or metal salt can be added to esterification product after esterification. In addition, crystallization temperature regulator, branching agent and / or metal salt can be added together with aliphatic dicarboxylic acid. In addition, crystallization temperature regulator, branching agent and / or metal salt can be fed to esterification supply line 200 after the first esterification and the second esterification.

[0262] Since the crystallization temperature regulator and / or the metal salt are fed into the esterification reaction, the crystallization temperature regulator and / or the metal salt may be uniformly dispersed in the first biodegradable resin.

[0263] The crystallization temperature regulator may have the above characteristics. In particular, nanocellulose may be used as a crystallization temperature regulator.

[0264] Nanocellulose can be pretreated by bead mill, ultrasound or high-speed dispersion at about 1000 rpm to about 1500 rpm before adding. Specifically, nanocellulose can be water-dispersed nanocellulose pretreated with a bead mill or pretreated with ultrasound.

[0265] First, a vertical mill or a horizontal mill can be used as a wet milling device for bead mill pretreatment. A horizontal mill is preferred because it allows more beads to be packed inside the chamber, reduces uneven wear of the machine, reduces bead wear, and makes maintenance easier, but the present invention is not limited thereto.

[0266] The bead mill pretreatment may be performed using one or more beads selected from the group consisting of zirconium, zircon, zirconia, quartz, and alumina.

[0267] In particular, beads having a diameter of about 0.3 mm to about 1 mm can be used for bead mill pretreatment. For example, the diameter of the beads can be about 0.3 mm to about 0.9 mm, about 0.4 mm to about 0.8 mm, about 0.45 mm to about 0.7 mm, or about 0.45 mm to about 0.6 mm.

[0268] When the diameter of the beads satisfies these ranges, the dispersibility of the nanocellulose can be further improved. When the diameter of the beads exceeds these ranges, the average particle size and particle size deviation of the nanocellulose may increase, resulting in lower dispersibility.

[0269] In addition, for the bead mill pretreatment, it is preferred to use beads having a higher specific gravity than nanocellulose because sufficient energy can be transferred. For example, the beads may be one or more selected from the group consisting of zirconium, zircon, zirconium oxide, quartz and alumina, which have a higher specific gravity than water-dispersible nanocellulose, and preferably zirconium beads having a specific gravity more than 4 times higher than that of water-dispersible nanocellulose, but the present invention is not limited thereto.

[0270] In addition, the ultrasonic pretreatment is a method of physically breaking or pulverizing nanoparticles using waves generated by emitting 20 kHz ultrasound into a solution.

[0271] Ultrasonic pretreatment can be carried out less than 30 minutes at an output of 30000J / s or less. For example, ultrasonic pretreatment can be carried out at an output of 25000J / s or less or 22000J / s or less for 25 minutes or less, 20 minutes or less or 18 minutes or less. When output and execution time meet above-mentioned scope, the influence of ultrasonic pretreatment can be maximized, that is, the improvement of dispersibility. When the amount of energy exceeds above-mentioned scope, nanoparticles can be reunited, and dispersibility can be reduced.

[0272] The nanocellulose according to the embodiment can be pretreated with a bead mill, or can be pretreated with ultrasound. Alternatively, the nanocellulose according to the embodiment can have been pretreated with a bead mill and pretreated with ultrasound. Here, it is preferred to perform ultrasound pretreatment after bead mill pretreatment to prevent reagglomeration and improve dispersibility.

[0273] The nanocellulose according to the embodiment can be pretreated with a bead mill or ultrasonically pretreated. Alternatively, the nanocellulose according to the embodiment can have been pretreated with a bead mill and ultrasonically pretreated. Here, ultrasonic pretreatment is preferably performed after bead mill pretreatment to prevent reagglomeration and improve dispersibility.

[0274] Since nanocellulose includes ionic metal, it has high dispersibility in water. In addition, by bead mill pretreatment and / or ultrasonic pretreatment, an aqueous dispersion of nanocellulose with high dispersibility can be obtained. In the nanocellulose aqueous dispersion, the content of nanocellulose can be about 1wt% to about 50wt%.

[0275] In the esterification reaction, a titanium-based catalyst and / or a germanium-based catalyst may be used. In particular, a titanium-based catalyst and / or a germanium-based catalyst may be added to the slurry, and the esterification reaction may be performed.

[0276] Furthermore, before the first esterification reaction, a titanium-based catalyst and / or a germanium-based catalyst may be added to the slurry, and the titanium-based catalyst and / or the germanium-based catalyst may be further added to the product of the first esterification reaction.

[0277] The first biodegradable resin may include one or more titanium-based catalysts selected from the group consisting of titanium isopropoxide, antimony trioxide, dibutyltin oxide, tetrapropyl titanate, tetrabutyl titanate, tetraisopropyl titanate, antimony acetate, calcium acetate, and magnesium acetate, or one or more germanium-based catalysts selected from the group consisting of germanium oxide, germanium methoxide, germanium ethoxide, tetramethyl germanium, tetraethyl germanium, and germanium sulfide.

[0278] In addition, based on the total weight of glycol, aromatic dicarboxylic acid and aliphatic dicarboxylic acid, the content of the catalyst can be about 100ppm to 1000ppm. For example, a titanium-based catalyst or a germanium-based catalyst of about 100ppm to about 800ppm, about 150ppm to about 700ppm, about 200ppm to about 600ppm or about 250ppm to about 950ppm can be included. Because the content of the catalyst meets the scope, the characteristics can be further improved.

[0279] In addition, before the esterification reaction, a heat stabilizer can be added together with the slurry. In the middle of the esterification reaction, the heat stabilizer can be fed into the esterification supply line 200. After the esterification reaction, the heat stabilizer can be fed into the esterification product. In addition, the heat stabilizer can be added together with the aliphatic dicarboxylic acid. In addition, after the first esterification and before the second esterification, the heat stabilizer can be fed into the esterification supply line 200.

[0280] The characteristics of the heat stabilizer may be the same as described above.

[0281] Based on the total weight of glycol, aromatic dicarboxylic acid and aliphatic dicarboxylic acid, the content of heat stabilizer can be 3,000ppm or less. In particular, based on the total weight of glycol, aromatic dicarboxylic acid and aliphatic dicarboxylic acid, the content of heat stabilizer can be, for example, 10ppm to 3,000ppm, 20ppm to 2,000ppm, 20ppm to 1,500ppm or 20ppm to 200ppm. Since the content of heat stabilizer meets the range, the polymer degradation caused by high temperature during the reaction can be controlled, so the terminal groups of the polymer can be reduced and the color can be improved.

[0282] After the esterification reaction is completed, at least one selected from the group consisting of additives (such as silicon dioxide, potassium or magnesium) and color correction agents (such as cobalt acetate) may be further added to the esterification reaction product. That is, after the esterification reaction is completed, the additives and / or color correction agents may be added and stabilized, and then the polycondensation reaction may be performed. The additives and / or color correction agents may be added after the esterification reaction is completed, and may be fed into the polycondensation supply line 300 together with the prepolymer. Therefore, the additives and / or color correction agents may be uniformly dispersed in the first biodegradable resin.

[0283] In addition, after the esterification reaction is completed, an inorganic filler can be added to the esterification reaction product. That is, after the esterification reaction is completed, the inorganic filler is added and stabilized, and then a polycondensation reaction can be performed. The characteristics of the inorganic filler are the same as described above. The inorganic filler can be fed into the polycondensation supply line 300 together with the prepolymer, and a polycondensation process can be performed. Therefore, the inorganic filler can be uniformly dispersed in the first biodegradable resin.

[0284] In addition, the first recoverer 510 recovers reaction byproducts such as water from the esterification supply line 200. The first recoverer 510 may apply vacuum pressure or reflux to the esterification supply line 200 to recover byproducts generated in the esterification reaction.

[0285] The method for preparing the first biodegradable resin includes the step of polycondensing a prepolymer. The polycondensation reaction can be performed as follows.

[0286] The prepolymer is fed into the polycondensation supply line 300. In addition, a crystallization temperature regulator, a heat stabilizer, at least one color correction agent, an inorganic filler, a metal salt, and other additives may be fed into the polycondensation supply line 300 together with the prepolymer.

[0287] Furthermore, a prepolymer may be fed into the polycondensation supply line, and a polycondensation reaction of the prepolymer may be performed.

[0288] The polycondensation reaction can be carried out at about 180° C. to about 280° C. and about 10 torrs or less for about 1 hour to about 3 hours. For example, the polycondensation reaction can be carried out at about 190° C. to about 270° C., about 210° C. to about 260° C., or about 230° C. to about 255° C., at about 0.9 torrs or less, about 0.7 torrs or less, about 0.2 torrs to about 10 torrs, about 0.2 torrs to about 0.9 torrs, or about 0.2 torrs to about 0.6 torrs for about 1.5 hours to about 3 hours, about 1.5 hours to about 3 hours, or about 1.5 hours to about 2.5 hours.

[0289] Furthermore, the polycondensation reaction may include a first polycondensation and a second polycondensation.

[0290] For example, the first polycondensation can be carried out at a temperature of about 260° C. or less, about 250° C. or less, about 215° C. to about 250° C., about 215° C. to 245° C., or about 230° C. to about 245° C., at about 1 torr to about 200 torrs, about 2 torrs to about 100 torrs, about 4 torrs to about 50 torrs, about 5 torrs to about 45 torrs, or about 8 torrs to about 32 torrs, for about 0.5 hour to about 2 hours, about 0.5 hour to about 1.5 hours, or about 0.5 hour to about 1 hour.

[0291] In addition, the second polycondensation can be carried out at about 220° C. to about 265° C., about 230° C. to about 260° C., or about 235° C. to about 255° C., at about 1 torr or less, about 0.8 torrs or less, about 0.6 torrs or less, about 0.1 torrs to about 1 torrs, about 0.2 torrs to about 0.8 torrs, or about 0.2 torrs to about 0.6 torrs, for about 0.5 hour to about 2 hours, about 0.5 hour to about 1.5 hours, or about 1 hour to about 1.5 hours.

[0292] In addition, before the polycondensation reaction, a titanium-based catalyst or a germanium-based catalyst may be further added to the prepolymer. In addition, before the polycondensation reaction, one or more types selected from the group consisting of an additive (such as silicon dioxide, potassium or magnesium); an amine-based stabilizer (such as trimethyl phosphate, triphenyl phosphate, trimethylphosphine, phosphoric acid, phosphorous acid or tetraethylenepentamine); and a polymerization catalyst (such as antimony trioxide, antimony trioxide or tetrabutyl titanate) may be further added to the prepolymer.

[0293] The number average molecular weight of the polymer can be about 10000 g / mol to about 60000 g / mol, about 15000 g / mol to about 50000 g / mol, about 15000 g / mol to about 40000 g / mol, about 20000 g / mol to about 35000 g / mol or about 20000 g / mol to about 30000 g / mol. When the number average molecular weight of the polymer meets the range, the first biodegradable resin composition can be easily spun.

[0294] In addition, the second recoverer 520 recovers reaction byproducts such as water from the polycondensation supply line 300. The second recoverer 520 may apply vacuum pressure to the polycondensation supply line 300 and may recover byproducts generated by the polycondensation reaction.

[0295] The second recoverer 520 may apply a vacuum pressure of about 0.1 torr to about 1 torr or a vacuum pressure of about 0.1 torr to about 0.9 torr to the inside of the polycondensation supply line 300 .

[0296] Next, an anti-hydrolysis agent and / or a chain extender are added to the polymer. Next, the polymer, the anti-hydrolysis agent and the chain extender are uniformly mixed and maintained at about 200° C. to about 260° C. for about 1 minute to about 15 minutes. Thus, the polymer reacts with the anti-hydrolysis agent and / or the chain extender.

[0297] Alternatively, an anti-hydrolysis agent and / or a chain extender may be added to the polycondensation supply line 300 through a static mixer and may react with the polymer. The reaction temperature of the anti-hydrolysis agent and / or the chain extender in the polycondensation supply line 300 may be about 200° C. to about 260° C. In addition, the reaction time of the anti-hydrolysis agent and / or the chain extender in the polycondensation supply line 300 may be about 1 minute to about 15 minutes.

[0298] The anti-hydrolysis agent may have the above-mentioned characteristics.

[0299] The chain extender may have the characteristics described above.

[0300] Therefore, the first biodegradable resin composition can have an appropriate degree of hydrolysis and high biodegradability.

[0301] Next, pellets can be produced from the polymer.

[0302] Specifically, the polymer may be cooled to about 15°C or less, about 10°C or less, or about 6°C or less, and then the cooled polymer may be cut to produce pellets. Alternatively, the polymer may be cut at about 40°C to about 60°C.

[0303] The cutting step may be performed without limitation using any pellet cutting machine used in the industry, and the pellets may have various shapes. The pellet cutting method may include an underwater cutting method or a wire cutting method.

[0304] The pellets may undergo additional post-processing processes. The pellets may be placed into a post-processor 400 and a post-processing process may be performed.

[0305] The post-processing process may be performed in the post-processor 400. The pellets are fed into the post-processor 400. Next, the post-processor 400 may melt the fed pellets by friction heating and re-extrude them. That is, the post-processor 400 may include an extruder, such as a twin-screw extruder.

[0306] The temperature of the post-treatment process may be about 230°C to about 270°C. The temperature of the post-treatment process may be about 230°C to about 260°C. The temperature of the post-treatment process may be about 240°C to about 265°C. The temperature of the post-treatment process may be about 240°C to about 260°C.

[0307] The time of the post-treatment process can be about 30 seconds to about 3 minutes. The time of the post-treatment process can be about 50 seconds to about 2 minutes. The time of the post-treatment process can be about 1 minute to about 2 minutes.

[0308] Next, the resin extruded by the extruder can be cooled, cut and processed into pellets for post-treatment. That is, the resin extruded by the extruder can be reprocessed into pellets through the above-mentioned cutting step.

[0309] During post-treatment, the crystallinity of the pellets can be improved.

[0310] The biodegradability of the first biodegradable resin composition can be measured by the following method.

[0311] To measure biodegradability, the biodegradable resin composition was mixed with compost and subjected to an accelerated biodegradation test at 60°C and 90% humidity. After a certain period of time, the number average molecular weight of the first biodegradable resin composition was measured using gel permeation chromatography (GPC). The biodegradability was obtained by dividing the difference between the initial number average molecular weight and the number average molecular weight after a certain period of biodegradation by the initial number average molecular weight.

[0312] Biodegradability can be expressed by the following equation 1:

[0313] [Equation 1]

[0314]

[0315] Here, the first biodegradable resin composition is mixed with compost and subjected to an accelerated biodegradation test at a temperature of 60° C. and a humidity of 90% for a certain period of time. The initial number average molecular weight of the first biodegradable resin composition before the accelerated biodegradation test and the number average molecular weight of the first biodegradable resin composition that has been subjected to the accelerated biodegradation test for a certain period of time are measured by gel permeation chromatography (GPC).

[0316] The biodegradability was calculated by dividing the difference between the initial number average molecular weight and the number average molecular weight after a certain period of biodegradation by the initial number average molecular weight.

[0317] In addition, the compost may include about 40 wt % of pig manure, about 15 wt % of chicken manure, about 37 wt % of wood chips, about 5 wt % of zeolite, and about 3 wt % of microbial agent.

[0318] In addition, the producer of the compost is Taeheung F&G, and the product name of the compost is Geosaengto (1st-grade compost by-product fertilizer).

[0319] In addition, in order to measure biodegradability, the first biodegradable resin composition is produced into a sheet having a thickness of about 300 μm. Next, the produced sheet is cut into a size of about 30 mm×30 mm to produce a thin sheet. The thin sheet may be mixed with compost and an accelerated biodegradation test may be performed.

[0320] In the first biodegradable resin composition, the biodegradability after one week may be about 40% to about 70%, about 45% to about 65%, about 47% to about 63%, or about 49% to about 62%.

[0321] In the first biodegradable resin composition, the biodegradability after two weeks may be about 50% to about 70% or about 55% to about 68%.

[0322] In the first biodegradable resin composition, the biodegradability after three weeks may be about 63% to about 75% or about 63% to about 73%.

[0323] In the first biodegradable resin composition, the biodegradability after four weeks may be about 73% to about 85% or about 75% to about 82%.

[0324] In the first biodegradable resin composition, the biodegradability after six weeks may be about 80% to about 90% or about 82% to about 88%.

[0325] In the first biodegradable resin composition, the biodegradability after nine weeks may be greater than about 85%, greater than about 87%, greater than about 88%, greater than about 89%, or greater than about 90%.

[0326] The degree of hydrolysis of the first biodegradable resin composition may be measured by the following method.

[0327] In order to measure the degree of hydrolysis, the biodegradable resin composition according to the embodiment is immersed in water (100% RH) at 80°C, and then an accelerated hydrolysis test is performed. After a certain period of time, the number average molecular weight of the first biodegradable resin composition is measured using gel permeation chromatography (GPC). The degree of hydrolysis is obtained by dividing the difference between the initial number average molecular weight and the number average molecular weight after a certain period of biodegradation by the initial number average molecular weight.

[0328] Biodegradability can be expressed by the following equation 2:

[0329] [Equation 2]

[0330]

[0331] Here, the first biodegradable resin composition is immersed in water at 80° C. and then subjected to an accelerated hydrolysis test for a certain period of time. The initial number average molecular weight of the first biodegradable resin composition before the accelerated hydrolysis test and the number average molecular weight of the first biodegradable resin composition that has been subjected to the accelerated hydrolysis test for a certain period of time are measured by gel permeation chromatography (GPC).

[0332] The degree of hydrolysis was calculated by dividing the difference between the initial number average molecular weight and the number average molecular weight after a certain period of biodegradation by the initial number average molecular weight.

[0333] In addition, in order to measure the degree of hydrolysis, the first biodegradable resin composition was produced into a sheet having a thickness of about 300 μm. Next, the produced sheet was cut into a size of about 30 mm×30 mm to produce a thin sheet. The thin sheet was immersed in warm water and subjected to an accelerated hydrolysis test.

[0334] In the first biodegradable resin composition, the degree of hydrolysis after one week may be about 40% to about 65% or about 45% to about 63%.

[0335] In the first biodegradable resin composition, the degree of hydrolysis after two weeks may be about 80% to about 93% or about 85% to about 92%.

[0336] In the first biodegradable resin composition, the degree of hydrolysis after three weeks may be about 90% to about 97% or about 91% to about 96%.

[0337] In the first biodegradable resin composition, the degree of hydrolysis after four weeks may be about 92% to about 99% or about 93% to about 97%.

[0338] In the first biodegradable resin composition, the degree of hydrolysis after six weeks may be greater than about 94% or greater than about 95%.

[0339] In the first biodegradable resin composition, the degree of hydrolysis after nine weeks may be greater than about 95% or greater than about 96%.

[0340] Since the first biodegradable resin composition has a degree of hydrolysis and a hydrolysis increase rate within the above range, the first biodegradable resin composition can have sufficient durability in daily life areas and can be easily hydrolyzed when discarded. That is, since the first biodegradable resin composition has a degree of hydrolysis and a hydrolysis increase rate within an appropriate range, it can have sufficient hydrolysis resistance when used for yarns, etc. In addition, when the first biodegradable resin composition is not only discarded in the soil, but also discarded in a river or the ocean, after a sufficient time, the first biodegradable resin composition can be easily decomposed by hydrolysis, biodegradation, etc.

[0341] In addition, the first biodegradable resin composition may have an acid value of about 0.01 to about 3 mg KOH / g, about 0.1 to about 2.5 mg KOH / g, or about 0.1 to about 2.3 mg KOH / g.

[0342] Since the first biodegradable resin composition has an acid value within the above range, it may have the same hydrolysis characteristics and biodegradation properties as described above.

[0343] In addition, the first biodegradable resin composition may have surface tension, water contact angle, diiodomethane contact angle, surface free energy, dispersibility, and polarity.

[0344] Surface tension, water contact angle, diiodomethane contact angle, surface free energy, dispersibility and polarity can be measured on the surface of polyester sheets.

[0345] In the first biodegradable resin composition, the surface tension may be about 30 dynes to about 55 dynes. In the first biodegradable resin composition, the surface tension may be about 35 dynes to about 50 dynes.

[0346] In the first biodegradable resin composition, the water contact angle may be about 60° to about 90°, about 65° to about 85°, or about 67° to about 80°.

[0347] In the first biodegradable resin composition, the diiodomethane contact angle may be about 20° to about 40° or about 20° to about 35°.

[0348] In the first biodegradable resin composition, the surface free energy may be about 40 mN / m to about 60 mN / m or about 42 mN / m to about 55 mN / m.

[0349] In the first biodegradable resin composition, the dispersibility may be about 35 mN / m to about 55 mN / m or about 40 mN / m to about 50 mN / m.

[0350] In the first biodegradable resin composition, the polarity may be about 2 mN / m to about 8 mN / m or about 3 mN / m to about 7 mN / m.

[0351] Due to the composition of the first biodegradable resin, oligomer, crystallization temperature regulator, chain extender, metal salt, anti-hydrolysis agent, thermal stabilizer, etc., and processes such as esterification reaction, polycondensation reaction, chain extension reaction and heat treatment reaction, the first biodegradable resin composition can have a surface tension, water contact angle, diiodomethane contact angle, surface free energy, dispersibility and polarity within the above ranges. Therefore, the first biodegradable resin composition can have an appropriate degree of hydrolysis and appropriate biodegradability.

[0352] Furthermore, since the first biodegradable resin composition has the above-described surface characteristics, the biodegradable yarn according to the embodiment may be made of a nonwoven fabric or the like, and may easily absorb moisture or the like from the outside.

[0353] The first biodegradable resin composition may have a crystallization temperature of about 50°C to about 90°C, a crystallization temperature of about 45°C to about 90°C, a crystallization temperature of about 50°C to about 80°C, a crystallization temperature of about 40°C to about 80°C, a crystallization temperature of about 50°C to about 75°C, or a crystallization temperature of about 55°C to about 75°C.

[0354] In addition, the first biodegradable resin composition may have a crystallization temperature of about 50°C to about 130°C, a crystallization temperature of about 45°C to about 130°C, a crystallization temperature of about 50°C to about 120°C, a crystallization temperature of about 50°C to about 115°C, or a crystallization temperature of about 55°C to about 110°C.

[0355] In addition, the crystallization temperature of the first biodegradable resin composition may be 90° C. to 130° C., 95° C. to 130° C., 95° C. to 120° C., or 95° C. to 110° C. When these ranges are satisfied, yarns of a biodegradable nonwoven fabric made from the first biodegradable resin composition may not be broken, may include short fibers or long fibers having uniform diameters, and may improve tensile strength and elongation.

[0356] The first biodegradable resin composition may have a melting temperature. The melting temperature of the first biodegradable resin composition may be 120° C. to 200° C., 130° C. to 200° C., 150° C. to 200° C., or 150° C. to 190° C. When these ranges are met, the biodegradable nonwoven fabric made from the first biodegradable resin composition may have improved tensile strength and elongation.

[0357] The melting temperature can be measured according to the method for measuring the above-mentioned crystallization temperature.

[0358] The difference between the melting temperature of the first biodegradable resin composition and its crystallization temperature may be 30°C to 90°C, 30°C to 85°C, 35°C to 80°C, or 40°C to 75°C. The difference between the melting temperature of the first biodegradable resin composition and its crystallization temperature may be an indicator of the crystallization rate of the first biodegradable resin composition. When these ranges are met, excellent radioactivity of the first biodegradable resin composition may be ensured, and the occurrence of plying between produced biodegradable yarns may be suppressed.

[0359] The crystallization temperature can be measured by differential scanning calorimetry (DSC). The crystallization temperature (°C) of the first biodegradable resin composition can be measured by differential scanning calorimetry during a temperature increase from 40°C to 180°C at a rate of about 10°C / min and then cooled to -50°C at a rate of 10°C / min.

[0360] The crystallization temperature can be measured according to ASTM D3417. Specifically, in order to measure the crystallization temperature, differential scanning calorimetry (DSC) is used, the crystallization temperature is increased from 40°C to 200°C at a rate of 10°C / min, and then isothermal for 5 minutes to perform a first thermal history removal process, and then cooled from 200°C to -50°C at a rate of 10°C / min, and isothermal for 5 minutes to perform a second cooling process.

[0361] Since the first biodegradable resin composition has a crystallization temperature within the above range, it can be easily extruded and quickly crystallized during the yarn production process. Therefore, the biodegradable yarn according to the embodiment can be easily produced.

[0362] The first biodegradable resin composition may have a melt index.

[0363] The melt index of the first biodegradable resin composition at about 190° C. may be about 4 g / 10 minutes to about 40 g / 10 minutes. The melt index of the first biodegradable resin composition at about 190° C. may be about 5 g / 10 minutes to about 35 g / 10 minutes. The melt index of the first biodegradable resin composition at about 190° C. may be about 6 g / 10 minutes to about 30 g / 10 minutes.

[0364] The melt index of the first biodegradable resin composition at about 230°C may be about 16 g / 10 minutes to about 80 g / 10 minutes. The melt index of the first biodegradable resin composition at about 230°C may be about 17 g / 10 minutes to about 75 g / 10 minutes. The melt index of the first biodegradable resin composition at about 230°C may be about 18 g / 10 minutes to about 70 g / 10 minutes. The melt index of the first biodegradable resin composition at about 230°C may be about 20 g / 10 minutes to about 90 g / 10 minutes.

[0365] The melt index of the first biodegradable resin composition at about 250°C may be about 40 g / 10 minutes to about 120 g / 10 minutes. The melt index of the first biodegradable resin composition at about 250°C may be about 25 g / 10 minutes to about 110 g / 10 minutes. The melt index of the first biodegradable resin composition at about 250°C may be about 40 g / 10 minutes to about 110 g / 10 minutes. The melt index of the first biodegradable resin composition at about 250°C may be about 40 g / 10 minutes to about 100 g / 10 minutes.

[0366] Since the first biodegradable resin composition has a melt index within the above range, it can have improved spinning processability.Since the first biodegradable resin composition has a melt index within the above range, agglomeration or breakage can be prevented due to an improved spinning process.

[0367] The first biodegradable resin composition can have a melt index reduction (MID). The MID can be obtained by the following equation 3:

[0368] [Equation 3]

[0369] MID=(MI2-MI1) / (T2-T1)

[0370] wherein T1 is 190° C., T2 is 250° C., MI1 is the melt index when the temperature of the first biodegradable resin composition is T1, and MI2 is the melt index when the temperature of the first biodegradable resin composition is T2.

[0371] The MID of the first biodegradable resin composition may be about 0.4 g / 10 min°C to about 1.5 g / 10 min°C. The MID of the first biodegradable resin composition may be about 0.3 g / 10 min°C to about 1.5 g / 10 min°C. The MID of the first biodegradable resin composition may be about 0.5 g / 10 min°C to about 1.4 g / 10 min°C. The MID of the first biodegradable resin composition may be about 0.6 g / 10 min°C to about 1.3 g / 10 min°C.

[0372] Since the first biodegradable resin composition has an MID within the above range, it can be easily spun at high temperatures, and it can have appropriate mechanical strength at low temperatures. Therefore, the first biodegradable resin composition can improve processability when producing yarn.

[0373] Second biodegradable resin The composition may include a second biodegradable resin.

[0374] The second biodegradable resin may be at least one selected from the group consisting of polybutylene succinate, polylactic acid, polybutylene adipate, polybutylene succinate adipate, polybutylene succinate terephthalate, polyhydroxybutyrate-valerate, polycaprolactone, polybutylene succinate adipate terephthalate, and thermoplastic starch.

[0375] The second biodegradable resin may include polylactic acid.

[0376] The polylactic acid may be a high melting point polylactic acid having a stereocomplex crystal. In addition, the polylactic acid may be formed by solution mixing or melt mixing of poly-L-lactic acid and poly-D-lactic acid.

[0377] The polylactic acid may include a unit represented by the following Formula 8:

[0378] [Formula 8]

[0379]

[0380] Wherein the polylactic acid is a polymer comprising L-lactic acid units and / or D-lactic acid units. The polylactic acid may comprise poly-L-lactic acid and / or poly-D-lactic acid.

[0381] Poly-L-lactic acid can be a polymer mainly comprising L-lactic acid units.Poly-L-lactic acid can include L-lactic acid units with a content of about 90mol% to about 100mol%, about 95mol% to about 100mol% or about 97mol% to about 100mol%.Poly-L-lactic acid can include units other than D-lactic acid units and / or lactic acid.Poly-L-lactic acid can include units other than D-lactic acid units and / or lactic acid with a content of about 0mol% to about 10mol%, about 0mol% to about 5mol% or about 0mol% to about 3mol%.

[0382] Poly D-lactic acid can be a polymer mainly comprising D-lactic acid units. Poly D-lactic acid can include a content of about 90 mol% to about 100 mol%, about 95 mol% to about 100 mol% or about 97 mol% to about 100 mol% D-lactic acid units. Poly D-lactic acid can include units other than L-lactic acid units and / or lactic acid. Poly D-lactic acid can include a content of about 0 mol% to about 10 mol%, about 0 mol% to about 5 mol% or about 0 mol% to about 3 mol% L-lactic acid units and / or units other than lactic acid.

[0383] Units other than lactic acid may be units derived from dicarboxylic acids, polyols, hydroxycarboxylic acids, lactones, etc., which have functional groups capable of forming two or more ester bonds, or units derived from various polyesters composed of various components, various polyethers, and various polycarbonates.

[0384] Examples of dicarboxylic acids include, for example, aliphatic polyols such as succinic acid, adipic acid, azelaic acid, sebacic acid, terephthalic acid, isophthalic acid, etc. Examples of polyols include ethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, octanediol, glycerin, sorbitan, neopentyl glycol, diethylene glycol, triethylene glycol, polyethylene glycol and polypropylene glycol, aromatic polyols obtained by adding ethylene oxide to bisphenol, and the like.

[0385] Examples of hydroxycarboxylic acids include glycolic acid, hydroxybutyric acid, etc. Examples of lactones include, for example, glycolide, ε-caprolactone glycolide, ε-caprolactone, β-propiolactone, δ-butyrolactone, β- or γ-butyrolactone, pivalolactone, δ-valerolactone, and the like.

[0386] Polylactic acid is available from Biomer, Inc. under the name BIOMER) Tm L9000 is commercially available. In addition, polylactic acid can be obtained from Natureworks LLC or Mitsui Chemical (LACEA TM) are commercially available. In addition, polylactic acid can be described in U.S. Patent Nos. 4,797,468, 5,470,944, 5,770,682, 5,821,327, 5,880,254, and 6,326,458, which are incorporated herein by reference in their entirety for all purposes.

[0387] The melting point of polylactic acid may be about 100° C. to about 240° C. The melting point of polylactic acid may be about 120° C. to about 220° C. The melting point of polylactic acid may be about 140° C. to about 200° C. The melting point of polylactic acid may be about 140° C. to about 180° C.

[0388] The crystallization temperature (Tc) of the polylactic acid may be about 50° C. to about 80° C. The crystallization temperature (Tc) of the polylactic acid may be about 55° C. to about 75° C.

[0389] The glass transition temperature (Tg) of the polylactic acid may be about 20° C. to about 80° C. The glass transition temperature (Tg) of the polylactic acid may be about 30° C. to about 70° C. The glass transition temperature of the polylactic acid may be about 40° C. to about 65° C. The melting point and glass transition temperature may be measured by differential scanning calorimetry (DSC) according to ASTM D-3417.

[0390] Since polylactic acid has a melting point and a glass transition temperature within the above range, the second biodegradable resin composition can be easily extruded. In addition, since polylactic acid has a melting point and a glass transition temperature within the above range, the biodegradable yarn according to the embodiment can have improved mechanical properties.

[0391] The number average molecular weight (Mn) of the polylactic acid may be from about 20,000 g / mole to about 160,000 g / mole. The number average molecular weight of the polylactic acid may be from about 30,000 g / mole to about 140,000 g / mole. The number average molecular weight of the polylactic acid may be from about 40,000 g / mole to about 120,000 g / mole.

[0392] The weight average molecular weight (Mw) of polylactic acid can be about 40,000 g / mole to about 200,000 g / mole. The weight average molecular weight of polylactic acid can be about 50,000 g / mole to about 180,000 g / mole. The weight average molecular weight of polylactic acid can be about 70,000 g / mole to about 160,000 g / mole.

[0393] The polydispersity index (Mw / Mn) of polylactic acid can be from about 1.0 to about 3.0. The polydispersity index of polylactic acid can be from about 1.1 to about 2.0. The polydispersity index of polylactic acid can be from about 1.2 to about 1.8. The weight average molecular weight and number average molecular weight can be measured by methods known to those skilled in the art. For example, the weight average molecular weight and number average molecular weight can be measured by gel permeation chromatography (GPC). The weight average molecular weight and number average molecular weight can be measured by standard monodisperse polystyrene.

[0394] Since the polylactic acid has a molecular weight and a polydispersity index within the above range, the second biodegradable resin composition can be easily extruded. In addition, since the polylactic acid has a molecular weight and a polydispersity index within the above range, the biodegradable yarn according to the embodiment can have improved mechanical properties.

[0395] The apparent viscosity of the polylactic acid measured at a temperature of about 190° C. and a shear rate of 1000 / s may be from about 50 Pascals (Pascal) seconds (Pa·s) to about 600 Pa·s. The apparent viscosity of the polylactic acid measured at a temperature of about 190° C. and a shear rate of 1000 / s may be from about 100 Pa·s to about 500 Pa·s. The apparent viscosity of the polylactic acid measured at a temperature of about 190° C. and a shear rate of 1000 / s may be from about 200 Pa·s to about 400 Pa·s.

[0396] The melt index of the polylactic acid at about 190°C may be about 3 g / 10 minutes to about 15 g / 10 minutes. The melt index of the polylactic acid at about 190°C may be about 4 g / 10 minutes to about 10 g / 10 minutes. The melt index of the polylactic acid at about 190°C may be about 6 g / 10 minutes to about 10 g / 10 minutes.

[0397] The melt index of the polylactic acid at about 220°C may be about 10 g / 10 minutes to about 30 g / 10 minutes. The melt index of the polylactic acid at about 220°C may be about 12 g / 10 minutes to about 25 g / 10 minutes. The melt index of the polylactic acid at about 220°C may be about 15 g / 10 minutes to about 25 g / 10 minutes.

[0398] The melt index of the polylactic acid at about 250°C may be about 30 g / 10 minutes to about 60 g / 10 minutes. The melt index of the polylactic acid at about 250°C may be about 35 g / 10 minutes to about 55 g / 10 minutes. The melt index of the polylactic acid at about 250°C may be about 40 g / 10 minutes to about 55 g / 10 minutes.

[0399] Since the polylactic acid has a viscosity and a melt index within the above range, the second biodegradable resin composition can be easily extruded. In addition, since the polylactic acid has a viscosity and a melt index within the above range, the biodegradable yarn according to the embodiment can have improved mechanical properties.

[0400] like Figure 5 and 6 As shown, the biodegradable yarn according to the embodiment can be produced by the following method.

[0401] Figure 5 A composite spinning machine for producing a biodegradable yarn according to an embodiment is shown.

[0402] The composite spinning machine may include two extruders 21 to melt the first biodegradable resin composition and the second biodegradable resin composition, respectively. The molten first and second biodegradable resin compositions may be discharged in appropriate amounts, respectively, by a metering pump 22. When the discharge amount is controlled, the component ratio of the first biodegradable resin composition to the second biodegradable resin composition may be controlled.

[0403] The discharged first biodegradable resin composition and the second biodegradable resin composition are supplied to the spinning block 23 through the metering pump 22, and, as Figure 5 As shown, the spin block 23 spins the first biodegradable resin composition and the second biodegradable resin composition to produce filaments 24 .

[0404] like Figure 6 As shown, the spin block 23 may spin the first biodegradable resin composition 42 and the second biodegradable resin composition 41 melted from the extruder 21 to the nozzle via the distribution plate 37 , thereby forming the filaments 24 .

[0405] More specifically, the second biodegradable resin composition 41 may flow in a flow path inside the distribution plate 37, and the first biodegradable resin composition 42 may flow through a flow path outside the distribution plate 37. When the first biodegradable resin composition 42 surrounds the second biodegradable resin composition 41, the filament (including the core and the sheath) may be spun by the spinneret 32. The spin block 23 may include a body 36, and the spinneret 32 ​​may be formed at the bottom of the body 36.

[0406] Alternatively, the distribution plate may be omitted.Therefore, the filaments in which the first biodegradable resin composition and the second biodegradable resin composition are mixed may be spun through a spinneret.

[0407] Although Figure 6A single filament is shown, but the spin block may include multiple discharge ports to obtain a desired number of filaments. The spun filaments may be solidified and crystallized in a cooling tank 25 .

[0408] An air cooling section may be provided between the spinneret 32 ​​and the cooling tank 25 of the spinning block 23. The length of the air cooling section may be about 0.5 cm to 100 cm. The length of the air cooling section may be about 1 cm to about 30 cm.

[0409] Undrawn yarn is produced from the solidified filaments. The undrawn yarn can be drawn by drawing device 26 and wound by winder 27. The drawn yarn can be heat treated at an appropriate temperature. The undrawn yarn can be drawn from about 1.5 times to about 6 times.

[0410] The extrusion temperature in the spinning block may be about 180° C. to about 250° C. The spinning speed in the spinning block may be about 1000 m / min to about 2000 m / min. The spinning thickness of the filaments may be about 2 deniers to about 10 deniers.

[0411] The tensile strength of the biodegradable yarn according to the embodiment may be about 1.5 gf / denier to about 6 gf / denier. The tensile strength of the biodegradable yarn according to the embodiment may be about 1.5 gf / denier to about 5 gf / denier. The tensile strength of the biodegradable yarn according to the embodiment may be about 1.5 gf / denier to about 4 gf / denier.

[0412] The elongation at break of the biodegradable yarn according to the embodiment may be about 20% to about 200%. The elongation at break of the biodegradable yarn according to the embodiment may be about 30% to about 200%. The elongation at break of the biodegradable yarn according to the embodiment may be about 40% to about 200%.

[0413] The tensile strength and elongation at break of the biodegradable yarn according to the embodiment may be measured according to ASTM D903.

[0414] The biodegradable resin composition according to an embodiment may include a first biodegradable resin composition including a first biodegradable resin, wherein the first biodegradable resin includes a diol, an aromatic dicarboxylic acid, and an aliphatic dicarboxylic acid.

[0415] Since the first biodegradable resin composition includes the first biodegradable resin, it may have properties suitable for spinning.

[0416] In particular, the first biodegradable resin composition may have an appropriate crystallization temperature. Therefore, the first biodegradable resin composition may be easily spun to produce a biodegradable yarn.

[0417] In addition, the first biodegradable resin composition may have an appropriate melt index. Therefore, the first biodegradable resin composition may be easily spun to produce a biodegradable yarn.

[0418] In addition, the first biodegradable resin composition may have an appropriate MID. Therefore, the first biodegradable resin composition may be easily spun to produce a biodegradable yarn.

[0419] In addition, the first biodegradable resin composition may have an appropriate number of carboxyl terminal groups. Therefore, the first biodegradable resin composition may be easily spun to produce a biodegradable yarn.

[0420] That is, the first biodegradable resin composition has the same crystallization temperature, melt index and MID as above, and it can be easily extruded through fine holes. In addition, since the decomposable resin composition has the same crystallization temperature, melt index and MID as above, it can be rapidly crystallized during the cooling process after the extrusion process, and the melt index can be increased. Therefore, the first biodegradable resin composition can have improved processability for yarn production.

[0421] In addition, since the first biodegradable resin composition has the same crystallization temperature as above, it can be easily compressed using appropriate heat and pressure. Therefore, the first biodegradable resin composition can be included on the surface of the biodegradable yarn according to the embodiment. Therefore, the biodegradable yarn according to the embodiment can be easily pressed together and easily applied to nonwoven fabrics or fabrics.

[0422] The contents will be explained in more detail by the following examples. However, the following examples are only for illustrating the present invention, and the scope of the present invention is not limited to these examples.

[0423] Production Example 1

[0424] Production of pretreated cellulose nanocrystals

[0425] Cellulose nanocrystals (NVC-100, manufacturer: Celluforce) in the form of dry powder with a particle size of about 1 μm to about 50 μm were dispersed in water in an amount of 1 wt %, and then sonicated for 1 minute using a tip-type ultrasonic disperser at an output of 20,000 J / s, thereby producing pretreated nanocellulose.

[0426] Production of biodegradable polyester resins

[0427] The first step: obtaining slurry through pretreatment

[0428] As shown in Table 1, pretreated nanocellulose, 1,4-butanediol (1,4-BDO) and terephthalic acid (TPA) were mixed at a molar ratio of 1.4:1 (1,4-BDO:TPA) and fed to a slurry tank (the bottom of the slurry tank was anchored, the height from the agitator was 40 mm, and three rotating blades were provided) in a non-catalyst state. Here, the D50 of terephthalic acid (TPA) was 100 μm. The content of nanocellulose was wt% based on the total raw material input.

[0429] Next, the mixture was pretreated by stirring at 60° C. and 100 rpm for 1 hour to obtain a slurry without phase separation.

[0430] Step 2: Obtaining prepolymer

[0431] The slurry obtained in the first step was fed to the reactor through a supply line, and 250 ppm of tetrabutyl titanate (Dupont, Tyzor TnBT product) was added thereto as a titanium-based catalyst. Next, the first esterification reaction was carried out at 220° C. and normal pressure for about 1 hour and 30 minutes until 95% of the by-product water was discharged.

[0432] 52 mol% of 1,4-butanediol (1,4-BDO) based on the total moles of diol, 40 mol% of adipic acid (AA) based on the total moles of dicarboxylic acid components, and 200 ppm of a titanium-based catalyst tetrabutyl titanate (Dupont, Tyzor TnBT product) based on the total weight of diol, aromatic dicarboxylic acid and aliphatic dicarboxylic acid were added to the reaction product, and then a second esterification reaction was performed at 210° C. and normal pressure for about 2 hours and 10 minutes until 95% of by-product water was discharged, thereby preparing a prepolymer having a number average molecular weight of 5500 g / mol.

[0433] The third step: polycondensation reaction

[0434] 150ppm of titanium-based catalyst tetrabutyl titanate (Dupont, Tyzor TnBT product) and 500ppm of triethyl phosphate stabilizer (based on the total weight of diols, aromatic dicarboxylic acids and aliphatic dicarboxylic acids) are added to the prepolymer obtained in the second step and stabilized for about 10 minutes. Next, the reaction mixture is heated to 240°C and then subjected to a 5-hour polycondensation reaction at 0.5 torrs to produce a polymer having a number average molecular weight of 25,000 g / mol. The produced polymer is cooled to 5°C and then cut using a pellet cutter to produce a biodegradable polyester resin composition.

[0435] Production Examples 2 to 5

[0436] The biodegradable polyester resin composition was produced under the conditions of the following Tables 1 to 3. For the remaining process conditions, reference is made to Production Example 1.

[0437] Example 1

[0438] Production of biodegradable polyester yarn

[0439] Biodegradable polyester resin composition and polylactic acid (NatureWorks, 4032D) produced in Production Example 1 are used to produce biodegradable polyester yarn. Polylactic acid is melted at about 240°C in the first extruder and fed into the distribution plate. The biodegradable polyester resin composition is melted at about 240°C in the second extruder and fed to the outside of the distribution plate. Next, the filaments in which the biodegradable polyester resin composition surrounds the polylactic acid are discharged through the nozzle of the spinning block. Here, the temperature of the spinning block is about 220°C. In addition, the weight ratio of the polylactic acid supplied to the spinning block to the biodegradable polyester resin composition is about 2: 1. In addition, the number of nozzles of the spinning block is 19. The spun filaments are cooled in a cooling tank at about 23°C, stretched about 3 times at about 100°C and wound. As a result, a biodegradable yarn according to an embodiment is produced.

[0440] Examples 2 to 5 and Comparative Examples 1 to 3

[0441] The biodegradable polyester yarn was produced under the conditions of the following Table 4. In Example 5, a mixture of Production Example 1 and polylactic acid was used. For the remaining process conditions, reference was made to Example 1.

[0442]

Table 1

[0443]

[0444]

Table 2

[0445]

[0446]

[0447]

Table 3

[0448]

[0449]

Table 4

[0450]

[0451] Evaluation Example

[0452] Evaluation Example 1: Crystallization Temperature

[0453] Using differential scanning calorimetry (DSC), the temperature was raised from 40°C to 180°C at a rate of 10°C / min, and then isothermal for 5 minutes to perform the first thermal history removal process. The second cooling process was performed by cooling from 180°C to -50°C at a rate of 10°C / min and isothermal for 5 minutes. The crystallization temperature (Tc) was confirmed in the second cooling process.

[0454] Evaluation Example 2: Melt Index

[0455] The melt index (g / 10 min) of the biodegradable polyester resin was measured at 190° C., 220° C., and 250° C. under a load of about 2.16 kg according to ASTM D1238. The specific conditions are as follows:

[0456] Equipment name: Melt flow index (WL 1400, Weed Lab)

[0457] Evaluation Example 3: Concentration of carboxyl terminal groups

[0458] 1 g of the biodegradable polyester resin was completely dissolved in 20 ml of o-cresol, diluted with 50 ml of chloroform, and titrated with a sodium hydroxide / methanol solution containing an indicator for measurement.

[0459] Evaluation Example 4: Molecular Weight

[0460] The number average molecular weights of the biodegradable resin compositions of Examples and Comparative Examples were measured using gel permeation chromatography (GPC).

[0461] Sample pretreatment: Dissolve 0.035 mg of PBAT chip in 1.5 ml of THF

[0462] Measuring device: waters, e2695

[0463] Flow rate: 1 ml / min, in THF\

[0464] Injection volume: 50 μl

[0465] Column temperature: 40°C

[0466] Detector: ELSD

[0467] Column: Styragel column HR 5E, HR4, HR2

[0468] Evaluation Example 5: Tensile Strength and Elongation at Break

[0469] The tensile strength and elongation at break of the biodegradable yarns produced in Examples and Comparative Examples were measured according to ASTM D903.

[0470] Evaluation Example 6: Biodegradability

[0471] For the biodegradable yarns produced in the examples and comparative examples, biodegradability was measured by measuring the amount of carbon dioxide generated according to KS M3100-1. In particular, an inoculum container containing only compost produced in a composting plant was prepared, and a test container was prepared in which a film was added to the compost in a volume of 5% by weight of the dry weight of the compost. Next, they were cultured for 180 days at a temperature of 58±2°C, a moisture content of 50%, and an oxygen concentration of 6% or more. The carbon dioxide generated from each container was captured and titrated with an aqueous phenolphthalein solution to measure the amount of carbon dioxide generated from each container. Based on the measured carbon dioxide generation, biodegradability was calculated according to the following equation 3.

[0472] [Equation 1]

[0473]

[0474] Evaluation Example 7: Processability

[0475] The processability of the biodegradable yarns in Examples and Comparative Examples was evaluated as follows:

[0476] Biodegradable yarn produced continuously in quantities of more than 1000 m: Good (O)

[0477] Biodegradable yarn breaks within 1000m: Poor (X)

[0478] Evaluation Example 7: Meltability

[0479] When a pressure of about 1 MPa was applied at about 80° C. for about 10 seconds, fusibility between the biodegradable yarns produced in Examples and Comparative Examples was observed with the naked eye.

[0480] Overall melting: good (O)

[0481] No melting: Poor (X)

[0482]

Table 5

[0483]

[0484]

Table 6

[0485]

[0486]

Table 7

[0487]

[0488] As shown in Tables 5 to 7, the biodegradable yarn according to the embodiment has improved mechanical properties, improved biodegradability, improved processability, and improved meltability.

[0489]

Symbol description

[0490] Filament 10, 11

[0491] Core 12

[0492] Leather 13

[0493] 100 Slurry Agitator

[0494] 200 Esterification supply line

[0495] 510 First Recycler

[0496] 520 Second Recycler

[0497] 300 Polycondensation supply line

[0498] 400 Postprocessor

[0499] 21 Extruder

[0500] 22 Metering Pumps

[0501] 23 Spinning Block

[0502] 24 Filament

[0503] 25 Cooling tank

[0504] 26 Stretching equipment

[0505] 27 Winder

[0506] 32 Spinneret

[0507] 36 Main Body

[0508] 37 Distribution Plate

[0509] 41. Second biodegradable resin composition

[0510] 42. A first biodegradable resin composition.

Claims

1. A biodegradable yarn comprising: a first biodegradable resin composition comprising a first biodegradable resin, wherein the first biodegradable resin comprises diol, aromatic dicarboxylic acid and aliphatic dicarboxylic acid, and The first biodegradable resin composition has a melt index of 6 to 15 g / 10 minutes at 190°C, and a crystallization temperature of 40 to 85°C.

2. The biodegradable yarn according to claim 1, comprising filaments, The filaments include: a core comprising a second biodegradable resin composition and having an elongated shape; and A sheath portion includes the first biodegradable resin composition and surrounds an outer peripheral surface of the core portion.

3. The biodegradable yarn according to claim 1, further comprising a second biodegradable resin composition, in, The second biodegradable resin composition includes at least one selected from the group consisting of polybutylene succinate, polylactic acid, polybutylene adipate, polybutylene succinate-adipate, polybutylene succinate terephthalate, polyhydroxybutyrate-valerate, polycaprolactone and polybutylene succinate adipate terephthalate.

4. The biodegradable yarn according to claim 1, wherein: The first biodegradable resin composition has a crystallization temperature of 45°C to 80°C.

5. The biodegradable yarn according to claim 1, wherein The first biodegradable resin composition has a melt index of 6 g / 10 min to 35 g / 10 min at 190° C.

6. The biodegradable yarn according to claim 1, wherein: The melt index reduction (MID) of the first biodegradable resin composition is 0.4 g / 10 min° C. to 1.5 g / 10 min° C., as represented by the following equation 1: Equation 1 MID=(MI2-MI1) / (T2-T1) Wherein, T1 is 190°C and T2 is 250°C, MI1 is the melt index when the temperature of the first biodegradable resin composition is T1, and MI2 is a melt index when the temperature of the first biodegradable resin composition is T2.

7. The biodegradable yarn according to claim 1, wherein: The biodegradable yarn has a tensile strength of 1.5 to 6 gf / denier and an elongation at break of 20 to 200%.

8. A biodegradable resin composition comprising: Biodegradable resin, Wherein, the biodegradable resin comprises diol, aromatic dicarboxylic acid and aliphatic dicarboxylic acid, and The biodegradable resin composition has a melt index of 6 to 15 g / 10 minutes at 190°C, and a crystallization temperature of 40 to 85°C.

9. The biodegradable resin composition according to claim 8, further comprising a crystallization temperature regulator.

10. The biodegradable resin composition according to claim 8, wherein The content of terminal groups in the biodegradable resin is 20 eq / ton or more and less than 60 eq / ton.

11. The biodegradable resin composition according to claim 8, wherein: The biodegradable resin composition has a melt index reduction (MID) of 0.4 g / 10 min° C. to 1.5 g / 10 min° C., which is represented by the following equation 1: Equation 1 MID=(MI2-MI1) / (T2-T1) T1 is 190°C, and T2 is 250°C, MI1 is the melt index when the temperature of the biodegradable resin composition is T1, and MI2 is a melt index when the temperature of the biodegradable resin composition is T2.

12. The biodegradable resin composition according to claim 8, wherein: The number average molecular weight of the biodegradable resin is 20000 g / mol to 35000 g / mol.

13. The biodegradable resin composition according to claim 8, wherein: The biodegradable resin composition has a melt index of 20 g / 10 min to 90 g / 10 min at 230° C.

14. The biodegradable resin composition according to claim 13, wherein: The biodegradable resin composition has a melt index of 40 g / 10 min to 120 g / 10 min at 250° C.

Citation Information

Patent Citations

  • Preparation of polylactic acid and copolymers of lactic acids

    US4797468A

  • Production of high molecular weight polylactic acid

    US5470944A

  • Method for producing polylactic acid

    US5770682A

  • Process for preparing polylactic acid

    US5821327A

  • Method for producing polylactic acid and apparatus used therefor

    US5880254A